DkHsfB2a/b-mediated regulatory network in high CO2 induced persimmon fruit deastringency - Rong Jin; Wei Wu; Xiao-fen Liu; Kun-song Chen; Xue-ren Yin (Postharvest Biology and Technology, 2026)

Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

Correction to: Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

MiR-4327 targets TP53 to promote cervical cancer cell proliferation - Mei-Lin Chen; Chen-Yang Chu; Feng-Xian Zhang; Li-Pei Zhang; Ying Yang; Bai-Zhao Peng; Chuang-Hai Wu; Xiao-Mei Chen; Yan-Ting You; Bing-Ying Rong; Hiu Yee Kwan; Xiao-Shan Zhao; et al. (Functional & Integrative Genomics, 2026)
Cervical cancer is a leading cause of female malignancy worldwide. While microRNA-4327 (miR-4327) has been implicated as a potential oncogene, its functional role and molecular mechanisms in cervical cancer pathogenesis remain unclear. This study aimed to determine the oncogenic function of miR-4327 and elucidate its downstream regulatory mechanism in cervical cancer pathogenesis. We measured miR-4327 expression in clinical cervical cancer tissues and cell lines using quantitative real-time PCR (qRT-PCR). We then assessed its effects on proliferation, migration, invasion, and cell cycle progression through functional assays including cell counting kit-8 (CCK-8), colony formation, transwell, and flow cytometry. To evaluate tumor growth in vivo, we established a xenograft model in non-obese diabetic (NOD)-severe combined immune-deficient (scid) mice. Using bioinformatic analysis and luciferase reporter assays, we identified TP53 as a direct target of miR-4327 and further validated this regulatory relationship with gain- and loss-of-function experiments. We found that miR-4327 was significantly upregulated in cervical cancer and promoted malignant phenotypes such as proliferation, migration, invasion, and cell cycle progression in vitro. Consistent with this, overexpression of miR-4327 accelerated tumor growth in vivo. Mechanistically, we confirmed TP53 as a direct functional target of miR-4327. Knocking down TP53 phenocopied the oncogenic effects of miR-4327, while restoring TP53 expression rescued the tumor-promoting effects mediated by miR-4327. These findings reveal a novel miR-4327/TP53 regulatory axis and nominate miR-4327 as a potential therapeutic target for intervention.

Root accumulation and efficient translocation of steroids in mangrove plants: Implications for an overlooked coastal reservoir - Ji-Xun Chen; Nian-Nian Wu; Shan Liu; Yuan Liu; Qin-Ge Zhou; Qing-Song Yang; Juan Ling; Xiao-Fang Huang; Yan-Kuan Tian; Chang-Gui Pan; Xiang-Rong Xu (Marine Pollution Bulletin, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

Ophiopogon japonicus fibrous root polysaccharides as stabilizers for zein-curcumin nanoparticles: Extraction-regulated structural conformations, antioxidant activities, and delivery performance - Jiaqi Chen; Xiao Yang; Wen Zhang; Yunlu Wei; Yisheng Jibu; Min Xia; Xiangyu Zeng; Shufan Xie; Rong Wang (Food Bioscience, 2026)

Crop-livestock system based on legume intercropping improves forage productivity, Tibetan sheep performance, and economic returns for farmers and herders: A regional integrated planting-feeding study - Chong Liang Luo; Hai-Xia Duan; Yong-Wei Chen; Mushtaq Ahmad; Xue-Ping Han; Hong-Jin Liu; Yong-Rong Fang; Fazal Ullah; Shi-Xiao Xu (European Journal of Agronomy, 2026)

Atomic scale porous Zn-doped carbon interlayers for high-performance Pt-ionomer interfaces - Weimin Zhou; Xiao Liu; Jianhua Wu; Hang Liu; Bin Shan; Rong Chen (Chemical Engineering Journal, 2026)

Persistent contamination, limited accumulation: In-situ isotope tracing reveals fast thallium turnover in natural waters - Chenghong Yu; Hongkai Wang; Wenze Xiao; Qiao-Guo Tan; Rong Chen; Lihua Liu; Nengwang Chen; Minwei Xie (Aquatic Toxicology, 2026)

Inoculation with phosphate-solubilizing bacteria reduce the transport of cadmium in Brassica napus L. by reshaping phosphate-solubilizing microbes in rhizosphere - Xiao Chen Zhang; Tong Yu Feng; Xiu Rong Tao; Lu Chen Wang; Jing Wen Kong; Yi Yao Mai; Yang Chen; Qing Guo; Long Guo; Chuan Jun Dai; Min Zhao (Rhizosphere, 2026)

In situ polymerization-prepared water-stable CsPbX3/PMMA composites for water-stimulated anti-counterfeiting and bioimaging - Rong Huang; Xiaoman Xiang; Danxia Zheng; Geyu Feng; Xinyu Ge; Rongze Zhu; Peng Chen; Xueling Chang; Xiao-Chun Hang; Xiaoyang Qi; Longfei Ruan (Chemical Engineering Journal, 2026)

In-situ generation and activation of H2O2 by synergistic dipole moment and multi-metal cycle for piezo-photocatalytic water cleanup - Zheng-Tao Dong; Long Sui; You Wu; Xiao-Ju Wen; Ya-Ya Yang; Yan-Rong Chen; Wen-Jun Wang; Hai Guo (Chemical Engineering Journal, 2026)

Heavy silicon isotope and mass-independent mercury isotope fractionation signals of Archean TTGs: Insights into the recycling of the silicified oceanic crust in the source region - Xiao Hu; Wenbin Zhu; Haizhen Wei; Runsheng Yin; Yongxiang Li; Yiwei Rong; Di Chen (Chemical Geology, 2026)

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Associations of High Serum Ferritin Concentrations with Learning Disability and Attention Deficit/Hyperactivity Disorder among Children and Adolescents - Xueya Xiao; Buyun Liu; Yuhong Xiong; Zelong Wangchen; Wei Bao; Shuang Rong; Meiyuan Chen; Yang Du; Linda G. Snetselaar; Guifeng Xu (Journal of the Academy of Nutrition and Dietetics, 2026)

Optimizing lipid retention for anaerobic membrane bioreactors treating food waste: Balancing methane enhancement and membrane fouling control - Luwei Yan; Shuangquan Zhao; Yu Xi; Yaqian Liu; Yuxin Xiao; Zhen Lei; Qian Li; Rong Chen (Bioresource Technology, 2026)

Temporin-GHaR6R Peptide Ameliorates Experimental Autoimmune Encephalomyelitis by Suppressing Microglial M1 Polarization and Mitochondrial Dynamics Dysfunction - Da-Qi Zhang; Hui-Min Xu; Jing Lu; Yu-Sheng Huang; Xiao-Li Feng; Li-Jun Chen; Wen-Jie Zhao; Rong Wang; Yingxia Zhang; Qifu Li (Probiotics and Antimicrobial Proteins, 2026)

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

Os79, a UDP‐Glycosyltransferase, negatively regulates cadmium tolerance and accumulation in rice - Rui Guo; Hao Yu Wang; Chong Wei Zhong; Rong Rong Ma; Jiu Huang; Jin Chen; Xian Jiao Guan; Lu Zheng; Ren Fang Shen; Ming Qing Liu; Xiao Fang Zhu (Journal of Hazardous Materials, 2026)

Latitudinal gradients shape adaptive divergence of tea saponin accumulation in Camellia oleifera - Danmei Yu; Liyun Feng; Suyun Zhang; Xiaohua Liu; Huan Yang; Jie Xiao; Shang Chen; Xia Dong; Li Cheng; Yao Zhao; Jun Rong; Jian Zhang (Food Bioscience, 2026)

Atomically dispersed Cu-doped TiO2 derived from MOF for photocatalytic hydrogen evolution - Hao Song; Hang Zhao; Xiao Yan; Xun Zhu; Rong Chen; Qiang Liao (Chemical Engineering Journal, 2026)

Multi-technique NMR analysis of liquid CO2 hydrate growth and pore structure evolution in sediments - Yu-Hao Bu; Yi-Fei Sun; Xiao-Cun Ma; Ling-Ban Wang; Zhen-Bin Xu; Yong-Yi Zhai; Jin-Rong Zhong; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2026)

Discovery of pyrrolo[2,3-d]pyrimidine derivatives with inhibitory effect on liver cancer stem cell - Xuecong Zhang; Xuechun Chen; Liwei Wang; Yiyuan Chang; Jiaxin Li; Jijian Yang; Dongxuan Ni; Ruihan Zhang; Rong Liu; Weilie Xiao (Medicinal Chemistry Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

Biochar aging-driven cadmium release in paddy soils: Mechanistic insights into adsorption capacity loss and biochar feedstock-specific risks - Ze-ning Yu; Xiao-qing Zhang; Fei-mei Chen; Rong-liang Qiu; Kuan Zhou; Xin-xian Long (Journal of Environmental Sciences, 2026)

Paraphlomis wui (Lamiaceae), a new species from Chongqing, China - Jing-Chen Yuan; Jin-Fei Xiao; Wei-Bin Xu; Si-Rong Yi; Chun-Lei Xiang; Ya-Ping Chen (Kew Bulletin, 2026)

Accumulation of recalcitrant dissolved organic matter during the formation of new North Pacific Intermediate Water in the Kuroshio-Oyashio confluence region - Lulu Han; Rong Huang; Ke Zeng; Xiao-Hua Zhang; Honghai Zhang; Zhaohui Chen; Peng Yao (Water Research, 2026)

A germline-specific vesicular structure licenses mRNA activation during spermiogenesis and is hijacked in gastric cancer - Mingxi Liu; Zerui Wang; Yinuo Li; Qingsong Xie; Zhuang Xiao; Xuezhi He; Guanxiong Wang; Yang Gao; Yini Zhang; Lin Zheng; Xun Xia; Lujie Chen; et al. (Science Bulletin, 2026)

Functional characterization of a canonical C-type lectin from Mytilus coruscus: Roles in innate immunity and feeding processes - Ying-rong Jin; Chuan-yue Chen; Ze-kai Wang; Pan Qin; Zhi Liao; Xiao-lin Zhang; Xiao-jun Yan (Fish & Shellfish Immunology, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Fe/Cu-γ-Al2O3 catalyst for pilot-scale internal circulation Fenton degradation of methyl orange: performance and mechanism - Dekai Fan; Yanran Lin; Peng Zhu; Yingwen Zhang; Bang Yao; Li Chao; Zhuangzhuang Jia; Jianjun Dai; Yingrui Ning; Rong Xiao; Chen Chen; Lei Gao; et al. (Journal of Environmental Management, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

Chronic Excessive Exposure to Fluoride Impairs the Intestinal Mucosal Barrier to Cause Inflammatory Response and Microbiome Dysbiosis in Rats - Jia-Rong Zhang; Yi-Wen Li; Hong-Xuan Chen; Yi Luo; Ru-Ming Liu; Jian-Bin Wang; Ning-Ning Liu; Jian-Hui Xiao (Biological Trace Element Research, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

Integrated sensing and communication for lettuce water-status monitoring - Ning Yang; Rong Du; Ni Yu; Wanting He; Zhenzhong Wang; Xiao Du; Si Chen (Computers and Electronics in Agriculture, 2026)

One-step phase separation and magnetic retrieval of switchable natural deep eutectic solvents via Fe3O4@CA composites for rapid extraction of illegal non-steroidal anti-inflammatory drugs in herbal extracts - Jin-Yue Dong; Rong-Jie Wang; Qing Ran; Xiao-Bei Yang; Wen-Chao Han; Feng-Qi Dong; Di Chen (Sustainable Chemistry and Pharmacy, 2026)

Structural characterization and prebiotic activity of oligosaccharides derived from sesame meal produced by different oil extraction methods - Hui-Fang Duan; Xiao-Rong Chen; Ran Zhang; Yuan-Qing Luo; Chang-Yong Lu; Ke-Qing Liu; Rui-Fu Cui; Run-Yang Zhang; Hua-Min Liu (Food Research International, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Microwave-assisted pyrolysis of dyeing sludge: Reaction kinetics, elemental transformation, and heavy metal migration - Dekai Fan; Rong Xiao; Wahab Nasarul; Chunbao Zhou; Yingwen Zhang; Bang Yao; Li Chao; Jianjun Dai; Gul Urooj; Yingrui Ning; Peng Zhu; Chen Chen; et al. (Chemical Engineering Journal, 2026)

Innovative utilization of waste printed circuit boards and coal gangue/ash for multifunctional glass-ceramics: structure-property insights via data-driven analysis - Yingwen Zhang; Lei Gao; Li Chao; Bang Yao; Dekai Fan; Chen Chen; Rong Xiao; Yingrui Ning; Peng Zhu; Urooj gul sandilo; Abeanezer Lukas Bassa; Nasarul Wahab; et al. (Chemical Engineering Journal, 2026)

Plant-soil feedback driven by root-associated fungal communities accelerates the secondary succession of bare saline-alkaline grassland patches - Xiaona Zheng; Yuhong Yin; Dan Yang; Jingjuan Bi; Wenlong He; Siya Li; Xiao Liang; Jigui Chen; Rong Wang; Zhiying Guo; Xing Li; Tao Zhang; et al. (Plant and Soil, 2026)

Juvenile-Onset Cerebrotendinous Xanthomatosis with Novel Compound Heterozygous CYP27A1 Mutations: Case Series and Literature Review - Kefang Du; Chunrong Wang; Linlin Wan; Zhao Chen; Hongyu Yuan; Qian Jiang; Xiao Dong; Daji Chen; Riwei Ouyang; Xiafei Long; Xiaokang Wu; Xinying Xiao; et al. (The Cerebellum, 2026)

Effects of mineral inputs on organic phosphorus (Adenosine 5′-monophosphate) sorption and implications for its biogeochemical behavior on marine sediments - Yu Meng; Meng Lv; Xiao-Tong Zhang; Xiao-Yan Cao; Rong Chen; Gui-Peng Yang (Marine Chemistry, 2026)

Distribution and potential drivers of methane emissions from deep-sea environments in Haima cold seep areas - Li Tang; Jing-Chun Feng; Can-Rong Li; Xiao Chen; Hui Zhang; Si Zhang (Frontiers in Marine Science, 2025)
Introduction Tracing methane originating from deep-sea environments is essential for understanding the global methane budget. However, knowledge regarding the mechanisms governing methane transfer from deep-sea sediments to the water column in cold seep environments remains limited. This study aims to quantitatively investigate the distribution of methane and identify its controlling factors within the Haima cold seep areas. Methods A comprehensive analysis was conducted to investigate the distribution characteristics of methane and its potential drivers in both the water column and sediment porewaters within the Haima cold seep areas. Results The key findings are: (1) Haima cold seeps serve as a methane source to the atmosphere, with pronounced spatial heterogeneity in emission strength across the monitored regions. (2) The vertical distribution of methane is influenced by multiple environmental factors. Key factors in sediment porewaters include sediment depth, porosity, inorganic carbon (IC), chloride (Cl – ), and sulfate (SO 4 2– ), whereas silicate (SiO 3 2– ) and dissolved oxygen (DO) are primary regulators in the water column. (3) Sediments represent a significant methane source for bottom seawater, with methane consumption being more pronounced in seepage areas than in non-seepage areas. Discussion This study demonstrates that methane dynamics in the Haima cold seep are complex and driven by a combination of physical, chemical, and biological processes across the sediment–water interface. The identified key drivers underscore the importance of porewater geochemistry and water column biogeochemistry in controlling methane release. These findings significantly advance our understanding of methane transport in deep-sea seep systems and provide crucial insights for refining global methane flux estimates.

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Utilization of river and lake dredged sediments for growing medium Preparation and its effect on the growth of alfalfa and bermudagrass: Germination, growth, and feasibility analysis - Rong Zhang; Xiangling Zhang; Bi Wu; Chen Wang; Jing Bai; Xuhao Li; Lingwei Kong; Zhouying Xu; Shilong Cao; Xinlu Xiao (Journal of Soils and Sediments, 2025)

Microbially carbon transformation in response to the partially replacement of chemical fertilizer by straw returning aggravates soil acidification in red paddy soil - Yingxi Chen; Changkuan Zhou; Xiangmin Rong; Xinyu Liu; Lian Zhang; Guoliang Jiang; Rusheng Xiao; Yongliang Han (Journal of Soils and Sediments, 2025)

ESG Scores and financial performance are making energy companies be in a dilemma: evidence from China - Fang-rong Ren; Hui-yi Chen; Xi-ting Yang; Xin-ge Guan; Xiao-yan Liu (Environment, Development and Sustainability, 2025)

A strain of mycovirus AaVV1 mediates hypovirulence of Alternaria species - Ya Rong Wang; Yi Chen; Chang Xin Li; Xiao Gang Li; Jun Zi Zhu; Jie Zhong (Pesticide Biochemistry and Physiology, 2025)

Carbohydrate-metabolizing gastrointestinal bacteria mediate resistome divergence in high feed efficiency Holstein dairy calves - Tianyu Chen; Shangru Li; Jianxin Xiao; Rong Peng; Mo Sha; Jingjun Wang; Jiaying Ma; Wei Wang; Mei Ma; Shengli Li; Zhijun Cao; Shuai Liu (Journal of Hazardous Materials, 2025)

A new framework integrating crop growth–level IV fugacity model and eco-indicator sensitivity to assess neonicotinoid fate and ecological risk in tropical rice–vegetable rotations - Huadong Tan; Xinyu Hu; Linxia Zhang; Yiru Chen; Rong Hao; Zhenzhen Wang; Chunyuan Wu; Xiaoying Zhang; Xiao Deng; Yi Li; Lin Wu; Yi Zhang (Journal of Hazardous Materials, 2025)

Morphology and nutrient content of bamboo rhizomes: Responses to enclosure succession in a Phyllostachys edulis forest in Wuyi Mountains, China - Xing Cai; Rui Cheng; Zhenhua Chen; Jiannan Lin; Min Wu; Jiaying Liu; Jihong Xiao; Yuchen Lin; Lingyan Chen; Yirong Zhang; Jundong Rong; Tianyou He; et al. (Forest Ecology and Management, 2025)

Preparation of high-performance ceramic conductive membranes and applications as the anode and cathode in electrochemical MBRs: antifouling performance and mechanisms - Jinzhuo Shi; Yisong Hu; Songhua Li; Wenqian Xiao; Rong Chen (Journal of Water Process Engineering, 2025)

Biotransformation causes the sex-specific regulation of polychlorinated biphenyls during metamorphosis of silkworm (Bombyx mori) and their effect on the silkworm development - Xue-Meng Qi; Xiao-Jun Luo; Pei-Xin Su; Peng-Peng Chen; Qing-Rong Yang; Yan-Hong Zeng; Bi-Xian Mai (Journal of Hazardous Materials, 2025)

Dual-nanostructured plasmonic Au-NS&NR/TiO2 for photothermal catalytic hydrogen production - Jianglin Tu; Jun Zhang; Hao Song; Xun Zhu; Dingding Ye; Yang Yang; Xiao Yan; Hong Wang; Rong Chen; Qiang Liao (Journal of Environmental Chemical Engineering, 2025)

Refining marine metal biomonitoring through insights into allometry in green mussels - Yuqing Liao; Haiyan Xiong; Wenze Xiao; Jun Liu; Minwei Xie; Rong Chen; Qiao-Guo Tan (Environmental Pollution, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Construction of LncRNA-miRNA-mRNA regulatory network in IgA nephropathy mice model by RNA-sequencing and bioinformatics analysis - Wen Jia Zheng; Tao Liu; Xiao Li Zhu; Yu Ting Zhang; Liang Bing Wei; Ya Chen Gao; Xing Xing Zhuang; Jia Rong Gao (Genes & Genomics, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Ten eudesmane sesquiterpenoids from Dobinea delavayi and their antimalarial and lipid-lowering activities - Wei Chen; Li-Tian Dong; Pei-Mi He; Wei-Juan Zu; Yi-Ling Yang; Rong Liu; Bei Jiang; Chao-Jiang Xiao (Phytochemistry, 2025)

Genome-wide association and epidemiological evidence linking air pollution to aging mechanisms - Xiao-Yu Liu; Dong Peng; Xu-Rui Liu; Yuan-Hui Sheng; Jun-Nan Zhao; Rong-Bin Xu; Dan Zhang; Bo Chen (Journal of Hazardous Materials, 2025)

Enrofloxacin drives the ultra-selective enrichment of Ca. Kuenenia stuttgartiensis under microaerobic conditions - Jiaqi Zhang; Hao Zhang; Zhenyi Ma; Lin Zhou; Qi Zhang; Quan Zhang; Chuan Chen; Rong Li; Xiao-Ming Ji (Journal of Hazardous Materials, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

Cambrian mid-ocean ridge basalt-like mafic rocks and associated boninites in the Dachadaban ophiolite from the North Qilian Block, northwest China: Petrogenesis and implications for back-arc extension - De-Chao Li; Xi-Jun Liu; Xiao Liu; Gang Chen; Qi Song; Hao Tian; Zheng-Lin Li; Peng-De Liu; Rong-Guo Hu (Geochemistry, 2025)

Evaluation of probiotic properties of lactic acid bacteria and physicochemical characteristics of fermented jujube (Ziziphus jujuba Mill.) polysaccharides - Rong Wang; Shufan Xie; Fei Li; Lanjian Qin; Jianming Ye; Jiaqi Chen; Xiao Yang; Yunlu Wei (Food Bioscience, 2025)

Elucidating the photodesorption mechanism of sulfamethoxazole on novel photo-responsive copper-phenylacetylide: Cleavage of π-π interactions and Cu O bonds - Rong Chen; Zhenjun Xiao; Zili Lin; Yishun Wang; Yu Chen; Ping Chen; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2025)

6-Methoxydihydrosanguinarine Suppresses the Proliferation of Non-small Cell Lung Cancer Cells through Elevation of ROS and Activation of IRE1/JNK Signaling - Xiao Qi; Chong Niu; Zi-zheng Zhang; Meng-ru Chen; Feng-ze Wang; Hong-rong Fei (Cell Biochemistry and Biophysics, 2025)

Optimal injection sites for therapeutic angiogenesis: HGF-mediated regulation of HIF-1α via MAPK/PI3K pathways in hypoxic endothelial cells - Peng Wang; Zhihua Rong; Fengshi Li; ShanShan Ma; Hongjuan Qiu; Wenzhuo Lian; Zongshu Li; Tianqi Chen; Qing Zhong; Wenjing Wang; Guoqiang Sun; ChangWei Liu; et al. (Tissue and Cell, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Electro-conductive nylon mesh assisted electro-chemical membrane bioreactor process (EMBR) for municipal wastewater treatment - Songhua Li; Yisong Hu; Jinzhuo Shi; Wenqian Xiao; Yuan Yang; Rong Chen (Journal of Water Process Engineering, 2025)

Corrigendum to “Removal of antibiotic resistance from wastewater in aquatic ecosystems dominated by submerged macrophytes” [J Hazard Mater 489 (2025) 137706] - Rong-min Zhang; Xiao-jie Chen; Ya-fei Li; Hui-zhen Tan; Wen-qing Huang; Ling-lin Li; Xin-ting Li; Jie Xie; Yun-xiao Chong; Xin-lei Lian; Xian-hui Huang (Journal of Hazardous Materials, 2025)

Novel galactose-rich polysaccharide from Ganoderma lucidum: structural characterization and immunomodulatory activities - Zhou-Wei Wu; Xiao-Cui Liu; Chen-Xi Quan; Xin-Yu Tao; Yi-Luo; Xue-Fang Zhao; Xing-Rong Peng; Ming-Hua Qiu (Carbohydrate Polymers, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

AHNAK2 Regulates NF-κB/MMP-9 Signaling to Promote Pancreatic Cancer Progression - Na-na Tang; Rong-bo Xu; Bo Jiang; Hai-ling Zhang; Xiao-song Wang; Dan-dan Chen; Ji-jun Zhu (Biochemical Genetics, 2025)

Ferritinophagy-derived iron causes protein nitration and mitochondrial dysfunction in acetaminophen-induced liver injury - Shi-Min Liang; Jie Shen; Rui-Ting Ma; Nan-Di Du; Rui Wang; Zuo-Min Wu; Min Shan; Shi-Rong Liang; Wei-Rong Hu; Wei Wang; Wei-Wei Sheng; De-Feng Huang; et al. (Toxicology and Applied Pharmacology, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

Hydrodynamic perturbations on contaminant behavior in low-permeability sediments: porewater metal dynamics and risk assessment implications - Ning Wang; Hongwei Hu; Wenze Xiao; Qiao-Guo Tan; Rong Chen; Minwei Xie; Stuart L. Simpson (Environmental Pollution, 2025)

Single and joint associations of exposure to polycyclic aromatic hydrocarbons with hypertensive disorders of pregnancy: A nested case-control study - Rui Yu; Cheng Chen; Mingyu Deng; Nian Wu; Yanling Xiao; Songlin An; Lin Tao; Xingting Zheng; Jing Yang; Zhongmei Hu; Pei Xu; Xingyan Liu; et al. (Environmental Pollution, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Removal of antibiotic resistance from wastewater in aquatic ecosystems dominated by submerged macrophytes - Rong-min Zhang; Xiao-jie Chen; Ya-fei Li; Hui-zhen Tan; Wen-qing Huang; Ling-lin Li; Xin-ting Li; Jie Xie; Yun-xiao Chong; Xin-lei Lian; Xian-hui Huang (Journal of Hazardous Materials, 2025)

Ambient air pollution and the risk of cancer: Evidence from global cohort studies and epigenetic-related causal inference - Dong Peng; Xiao-Yu Liu; Yuan-Hui Sheng; Si-Qi Li; Dan Zhang; Bo Chen; Pei Yu; Zhao-Yuan Li; Shuai Li; Rong-Bin Xu (Journal of Hazardous Materials, 2025)

Bismuth tungstate/graphite carbon nitride composites for efficient photocatalytic reduction of U(VI): Synthesis, performance, and mechanism - Yu-Jia Xiao; Shi Chen; Ping Li; Dong Zhang; Jing-Jing Wang; Hui Dong; Yan-Rong He (Journal of Environmental Chemical Engineering, 2025)

Valorizing pumpkin (Cucurbita moschata) seed meal into protein hydrolysates: Impact of different proteases on the structural, physicochemical, and functional properties - Liu Rong; Kefan Ouyang; Menglu Liu; Fangjie Xiao; Yushun Chen; Meng Wai Woo; Qiang Zhao (Food Bioscience, 2025)

Nectar characteristics and pollination ecology of Camellia perpetua in South China - Hai-du Jiang; Dan-juan Zeng; Hui-zhen Qin; Li-hui Peng; Yi-shan Yang; Zong-you Chen; Rong Zou; Jian-min Tang; Yun-sheng Jiang; Zhong-chen Xiong; Xiao Wei; Sheng-feng Chai (Flora, 2025)

Microwave-assisted pyrolysis of spent bleaching clay: A study of pyrolysis characteristics, kinetics, and intrinsic mechanism - Bang Yao; Li Chao; Yingwen Zhang; Yang Liu; Chunbao Zhou; Dekai Fan; Yunxiang Li; Pengfei Zhu; Wei Li; Yanran Lin; Lei Gao; Chen Chen; et al. (Chemical Engineering Journal, 2025)

SIRT3 deficiency reduces PFKFB3-driven T-cell glycolysis and promotes arthritic inflammation - Ting-Ting Wang; Taotao Han; Xinyue Xiao; Dan Guo; Xin Sun; Yudong Liu; Lidan Zhao; Haojie Xu; Rong Li; Lingjuan Jiang; Bo Zhang; Beidi Chen; et al. (Science China Life Sciences, 2025)

Wind Direction and Strength Determine the Genetic Structure of an Insect‐Pollinated Plant Across Heterogeneous Landscape - Jun‐Yin Deng; Rong‐Hua Fu; Stephen G. Compton; Chuan Yuan; Matthew M. Kling; Xiao‐Yong Chen; Yao‐Bin Song; Kai Jiang; Mei Liu; Jaco M. Greeff; Yan Chen (Journal of Biogeography, 2025)
Aim Dispersal of plant propagules and their genes is crucial for plant responses to landscape heterogeneities, yet the mechanisms behind this dispersal remain unclear. Ficus species depend on wind‐borne fig wasps for pollination, but research on airflow effects on Ficus genetic structure has produced conflicting results. Our study aims to clarify the role of wind in shaping the genetic structure of such plants with wind‐borne insect pollinators by examining how geomorphological complexity interacts with air movements to influence genetic structures. Location Southwest China: Sichuan, Yunnan, Guangxi and Guizhou provinces. Taxon Ficus tikoua Bur., Ficus , Moraceae. Methods We sampled 56 F. tikoua sites across southwest China, characterised by high geomorphologic complexity. River basins and predominant winds were visualised across the sampled regions. Wind connectivity between sampled sites during the main pollination season was modelled based on hourly daily wind data. The maternal and biparental genetic structure of sites were reconstructed using chloroplast DNA (cpDNA) and nuclear SSR (nuSSR) markers. Links between genetic structure, location, and wind parameters were estimated by Mantel or partial Mantel tests. Results The plant's maternal genetic structure was defined by river systems, with two distinct cpDNA groups located in the Yangtze and Pearl River basins, respectively. The boundaries for nuclear variation were less clearly delimited geographically. Sites with mixtures of nuSSR groups were concentrated where prevailing winds arrived from several directions. Stronger between‐site air flows increased nuSSR geneflow and genetic similarities, while populations receiving more wind flow were also more genetically variable. Main Conclusions Our study reveals how plant gene dispersal reflects air and water movements that in turn respond to geomorphologic complexity, thereby directly demonstrating the effects of wind on gene flow of plants with wind‐borne insect pollinators. Wind data matching pollinator flight times and large sample sizes are crucial for testing wind effects.

Experiment and analysis on dynamic characteristics of marine soft clay - Wenbin Xiao; Ke Wu; Wenbin Xu; Yajun Liu; Haijun Lu; Rong Chen (Marine Georesources & Geotechnology, 2025)

Recruitment of copiotrophic and autotrophic bacteria by hyperaccumulators enhances nutrient cycling to reclaim degraded soils at abandoned rare earth elements mining sites - Yong-He Han; Xi-Wen Cui; Hai-Yan Wang; Xiao-Bin Lai; Ying Zhu; Jia-Bing Li; Rong-Rong Xie; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2025)

Optimization strategy for Cr(VI) removal in coke-based modular constructed wetlands: A comprehensive analysis of purification efficiency, removal mechanisms, and practical feasibility - Xinlu Xiao; Xuhao Li; Xiangling Zhang; Chen Wang; Xiaoting Liu; Jing Bai; Rong Zhang; Shilong Cao; Jiezhou Hu; Zhenchao Liu; Jun Shen (Journal of Environmental Management, 2025)

Unraveling the impact of micro- and nano-sized polymethyl methacrylate on gut microbiota and liver lipid metabolism: Insights from oral exposure studies - Peng Chen Zheng; Xin Qiang Pan; Yi Jiong Zhou; Keng Po Lai; Rong Li; Xiao Xi Zhang (Environmental Pollution, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Self-powered and self-sensing water meter using contact-separation triboelectric nanogenerator with harvesting local head loss - Da-Qi Cao; Xiao-Dan Liu; Rong-Kun Fang; Guri Yihuo; Yun-Feng Wu; Zhan-Gao Huang; Wen-Yu Zhang; Xiangyu Chen; Xiao-Di Hao (Journal of Water Process Engineering, 2025)

Operational characteristics and phosphorus recycling potential of a hydroxyapatite (HAP)-anammox process at high nitrogen loading rate - Wenqian Xiao; Yisong Hu; Songhua Li; Jinzhuo Shi; Wenrui Tian; Yi Xue; Rong Chen (Journal of Environmental Chemical Engineering, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Isolation, characterization and biological activities of phenolics from the roots bark of Morus alba - Min Tan; Xiao-Cong Liu; Dan Liu; Xuan-Qin Chen; Rong-Tao Li; Zhi-Jun Zhang (Phytochemistry, 2025)

Accumulation of lipophilic and proteinophilic halogenated organic pollutants (HOPs) in the different types of feathers of laying hens - Xi Chen; Xiao-Jun Luo; Qun-Jie Feng; Yu Liu; Jun-Zhe Dai; Peng-Peng Chen; Pei-Xin Su; Qing-Rong Yang; Yan-Hong Zeng; Bi-Xian Mai (Journal of Hazardous Materials, 2025)

Herbaceous competition does not affect positive tree diversity effects on seedling crown complementarity - Muhammad Abdullah; Li-Ting Zheng; Li Zhang; Bai-Yu Yang; Xiao-Chen Fang; Di-Feng Bao; Samreen Ghulam Rasool; Ci-Liang Zhao; En-Rong Yan (Forest Ecology and Management, 2025)

Identification and differential expression analysis of microRNAs in the liver and spleen tissues of Yunnan Zebu and Holstein cattle - Rong Liu; Hesong Liu; Rong Li; Chunqing Li; Heng Xiao; Shanyuan Chen (Tropical Animal Health and Production, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Mechanistic insights into efficient phosphorus adsorption and recovery from water using functional ZnO/ZnFe-LDHs alginate hydrogels - Shilong Cao; Xiangling Zhang; Shuqin Xie; Chen Wang; Jing Bai; Xuhao Li; Rong Zhang; Xinlu Xiao; Jiezhou Hu; Xiaoxia Jiang (Journal of Environmental Chemical Engineering, 2025)

Design, synthesis and antifungal activity of novel pyrazole-amide-isothiazole derivatives as succinate dehydrogenase inhibitors - Ai-ling Bao; Xian-song Xie; De-yuan Wang; Zi-quan Deng; Yun Chen; Dan Liu; Wei-yi Li; Xiao-rong Tang; Wei Cheng; Ying-kun Yan (Food Chemistry, 2025)

Correction: Clinical, Microbiological, and Molecular Characterization of Candida (Starmera) stellimalicola, a Rare Fungal Pathogen Causing Human Infections - Xin Fan; Rong-Chen Dai; Xiao-Feng Yan; Zhong-Shan Tong; Jie Gong (Mycopathologia, 2025)

Draft Genome of Naganishia uzbekistanensis from a Clinical Pulmonary Infection - Rong-Chen Dai; Xin-Fei Chen; Xin Fan; Li Gu; Li Zhang; Dan Guo; Ying-Chun Xu; Meng Xiao (Mycopathologia, 2025)

Combination of herbal extracts regulates growth performance, liver and intestinal morphology, antioxidant capacity, and intestinal microbiota in Acrossocheilus fasciatus - Yi Ting Shen; Zhi Li Ding; Xiao Yan Wang; Wen Qi Chen; Rong Xing Xia; Shun Yang; Hui Fei (Aquaculture, 2025)

Methane seepage leads to a specific microplastic aging process in the simulated cold seep environment - Xiao Chen; Xiao-Nan Wu; Jing-Chun Feng; Bin Wang; Can-Rong Li; Yi-Lei Lin; Yong-Ji Huang; Song Zhong; Xiao-Chun Zhang; Jun-Lin Hu; Si Zhang (Journal of Hazardous Materials, 2025)

Effect of Maillard reaction on the allergenicity of crude extract of Mactra quadrangularis - Fa-Jie Li; Xin-Rong He; Dong-Xiao Li; Yang Yang; Shuai Kang; Qing-Mei Liu; Lian-Zhong Luo; Gui-Xia Chen; Guang-Ming Liu (Food Research International, 2025)

Protecting anthocyanins of postharvest blueberries through konjac glucomannan/low-acyl gellan gum coatings contained thymol microcapsule during low-temperature storage - Jing Xie; Dur E. Sameen; Zhenkun Xiao; Huiyan Zhu; Yunya Lai; Tingting Tang; Xingyu Rong; Fengmei Fu; Wen Qin; Mingrui Chen; Yaowen Liu (Food Chemistry, 2025)

Isolation, structural elucidation and biosynthetic pathway of bioactive prenyl quinone compounds from Panus lecomtei based on untargeted metabolomics combined with molecular networking - Si-Xian Wang; Bao-Song Chen; Zi-Juan Zhang; Shi-Rong Zhu; Xiao-Ling Wang; Gao-Qiang Liu (Food Chemistry, 2025)

Fast detection of NO2 by In2O3@ZnO nanofibers synthesized by coaxial electrospinning: Real-time monitoring application of smart mask - Xingyu Kang; Haibo Yu; Xiao Ma; Eryang Shang; Hong Chen; Huizhang Zhao; Jiawei Zhang; Rong Tan; Dong Wang; Hairui Fang (Chemical Engineering Journal, 2025)

Pollution status and assessment of seven heavy metals in the seawater and sediments of Hangzhou Bay, China - Rong Zhu; Yan-Yan Zeng; Li-Min Liu; Lu Yin; Kai-Ping Xu; Wei-Feng Chen; Shang-Chun Li; Xiao-Feng Zhou (Marine Pollution Bulletin, 2024)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Quality improvement of threadfin bream (Nemipterus virgatus) surimi-gel using soy protein as a natural food additive - Yi-Li Gao; Asami Yoshida; Jin-Yang Liu; Jing Yuan; Shinnosuke Maeda; Youjun Wang; Yan-Rong Jiang; Xiao-Mi Sun; Chao-Ping Chen; Yajun Wang; Tetsuhiko Okajima; Kiyoshi Osatomi (Food Chemistry, 2024)

Heavy metal pollution and ecological risk assessment of surface sediments covered by emerged and submerged plants in a shallow lake - Haizhu Liu; Junhong Bai; Kegang Zhang; Chen Wang; Jinfeng Liang; Ling Zhang; Yaqi Wang; Rong Xiao (Ecohydrology & Hydrobiology, 2024)

Bacterial community assembly in surface sediments of a eutrophic shallow lake in northern China - Bo Kuang; Rong Xiao; Chen Wang; Ling Zhang; Zhuoqun Wei; Junhong Bai; Kegang Zhang; Marco Campos; Milko A. Jorquera (Ecohydrology & Hydrobiology, 2024)

Lattice-Engineering modulated band structure facilitates enhanced stability of high-voltage LiCoO2 at 4.6 V - Zhi Zhang; Guang-Xin Wu; Zhou-Liang Tan; He-Zhang Chen; Zhen Yu; Zhen-Rong Yu; Xiao-Bing Huang; Wen-Jie Yang; Ying-De Huang (Chemical Engineering Journal, 2024)

Chemical constituents from noni (Morinda citrifolia L.) fruit juice and their chemotaxonomic significance - Yu-Qin Meng; Bin Zhang; Dong-Hui Zhang; Zhang-Xin Yu; Chun-Hua Long; Si-Rong Li; Xue-Na Zhang; Xiao-Bao Li; Guang-Ying Chen (Biochemical Systematics and Ecology, 2024)

Correction: A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Perfluorooctane sulfonate (PFOS) and benzo[a]pyrene (BaP) synergistically induce neurotoxicity in C6 rat glioma cells via the activation of neurotransmitter and Cyp1a1-mediated steroid hormone synthesis pathways - Yu-Shun Lu; Ju Chen; Xiao-Rong He; Shang-Lin Yang; Bing-Jie Ma; Jiang Yu; Jing Qiu; Yong-Zhong Qian; Yan-Yang Xu (Food and Chemical Toxicology, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Experimental studies and pore-scale modeling of hydrate dissociation kinetics at different depressurization rates in a cubic hydrate simulator - Chang-Wen Xiao; Xiao-Sen Li; Hong-Feng Lu; Gang Li; Chen-Lu Xu; Rong-Rong Qi; Dong-Hui Xing; Xian Li; Yi-Fan Weng; Lu Yu (Chemical Engineering Journal, 2024)

Catalytically ultrathin titania coating to enhance energy storage and release of aluminum hydride via atomic layer deposition - Zhijia Hu; Xingxing Xu; Huachen Shao; Ruidong Luo; Mingxuan Wang; Gen Tang; Xiao Liu; Bin Shan; Rong Chen (Chemical Engineering Journal, 2024)

Bioactives from biomass: Treasure for future potent antimicrobial applications - Weicheng Chen; Peng Zhang; Yucui Ding; Xiaobin Xie; Jianlong Fu; Rong Zhao; Yihan Xiao; Miodrag J. Lukic; Bin Li; Weishan Wang; Song Chen (Chemical Engineering Journal, 2024)

Biological exposure to microplastics and nanoplastics and plastic additives: impairment of glycolipid metabolism and adverse effects on metabolic diseases - Peng Chen Zheng; Rong Li; Keng Po Lai; Xiao Xi Zhang (Environmental Science and Pollution Research, 2024)

Enhanced solar-driven steam generation and water purification using 3D arch solar evaporators - Yong-Gang Wu; Chao-Hua Xue; Xiao-Jing Guo; Meng-Chen Huang; Hui-Di Wang; Chao-Qun Ma; Li Wan; Shi-Qiang Lv; Wen-Min Zhang; Rong-Rong Gao (Desalination, 2024)

The morphology of liquid CO2 hydrate films at different temperatures under saturation pressure - Yu-Jie Zhu; Yu Zhang; Yu-Zhou Chen; Yan Xie; Jin-Rong Zhong; Xiao-Hui Wang; Peng Xiao; Yi-Fei Sun; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2024)

Complete Genome Sequence of Candida mucifera from an Otitis Media Patient - Rong-Chen Dai; Jing Guan; Ya-Ting Ning; Timothy Kudinha; Wei Zhang; Xin-Fei Chen; Ge Zhang; Ying-Chun Xu; Meng Xiao (Mycopathologia, 2024)

A pooled mycoviral resource in a strain of Rhizoctonia solani are regulators of fungal virulence - Ya Rong Wang; Jia En Su; Zhi Juan Yang; Jie Zhong; Xiao Gang Li; Yi Chen; Jun Zi Zhu (Pesticide Biochemistry and Physiology, 2024)

Decapod iridescent virus 1 (DIV1) 168L can target cuticle protein 8 from Litopenaeus vannamei - Qin Zheng; Huan-huan Rao; Fu-Rong Zhao; Xiao-Juan Chen; Wei Wang; Jian-Ming Chen (Journal of Invertebrate Pathology, 2024)

Bamboo vinegar regulates the phytoremediation efficiency of Perilla frutescens (L.) Britt. by reducing membrane lipid damage and increasing cadmium retention - Zhenguo Li; Xingyu Hao; Tianlian He; Ying Chen; Mingwei Yang; Cheng Rong; Chengzhen Gu; Qingtie Xiao; Ruiyu Lin; Xinyu Zheng (Journal of Hazardous Materials, 2024)

Scalable thermochromic superhydrophobic collagen fiber-based wearable materials for all-weather self-adaptive radiative cooling and solar heating - Meng-Chen Huang; Chao-Hua Xue; Zhongxue Bai; Hui-Di Wang; Chao-Qun Ma; Yong-Gang Wu; Li Wan; Long Xie; Shi-Qiang Lv; Rong-Rong Gao; Wen-Min Zhang; Jun Cheng; et al. (Chemical Engineering Journal, 2024)

Copper-ion-complexed palygorskite as a novel nanozyme with enhanced peroxidase-like activity for sensitive colorimetric sensing - Ping Chen; Hui Zhong; Xiao-rong Li; Tingting Zhang; Xiang Wang; Fang Hu; Yubo Yan; Jiaxing Xu; Meisheng Li (Applied Clay Science, 2024)

Integrated Information for Pathogenicity and Treatment of Spiroplasma - Yixue You; Jianmin Xiao; Jiaxin Chen; Yuxin Li; Rong Li; Siyuan Zhang; Qichen Jiang; Peng Liu (Current Microbiology, 2024)

PANI/GO and Sm co-modified Ti/PbO2 dimensionally stable anode for highly efficient amoxicillin degradation: Performance assessment, impact parameters and degradation mechanism - Zeyi Wang; Luyao Zhang; Rong Su; Lu Yang; Feng Xiao; Lichuan Chen; Ping He; Dingming Yang; Yali Zeng; Yun Zhou; Ying Wan; Bin Tang (Journal of Environmental Management, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Draft Genome Sequence of Candida saopaulonensis from a Very Premature Infant with Sepsis - Ya-Ting Ning; Rong-Chen Dai; Zheng-Yu Luo; Meng Xiao; Yingchun Xu; Qun Yan; Li Zhang (Mycopathologia, 2024)
The rare fungus Candida saopaulonensis has never been reported to be associated with human infection. We report the draft genome sequence of the first clinical isolate of C. saopaulonensis, which was isolated from a very premature infant with sepsis. This is the first genome assembly reaching the near-complete chromosomal level with structural annotation for this species, opening up avenues for exploring evolutionary patterns and genetic mechanisms of pathogenesis.

A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

An injectable antibacterial hydrogel with bacterial-targeting properties for subcutaneous suppuration treatment - Yongchang Tian; Rong Zhang; Jiaming Cui; Yaowei Zhu; Minghui Sun; Ian W. Hamley; Chunsheng Xiao; Li Chen (Chemical Engineering Journal, 2024)

Contact-electro-catalysis for degradation of trace antibiotics in wastewater - Da-Qi Cao; Rong-Kun Fang; Yi-Xuan Song; Ming-Guo Ma; Haiyan Li; Xiao-Di Hao; Rongling Wu; Xiangyu Chen (Chemical Engineering Journal, 2024)

A new 1,4-benzoxazine derivative produced by endophytic Colletotrichum gloeosporioides B-142 - Bing Zhang; Zhi-pu Huang; Yu Si; Ke-tao Zhang; Xiao-rong Xu; Jian-hong Chen; Qing Zhao; Xiao-mei Zhang (Natural Product Research, 2024)

LSTM-based deformation forecasting for additional stress estimation of existing tunnel structure induced by adjacent shield tunneling - Xiao-Wei Ye; Si-Yuan Ma; Zhi-Xiong Liu; Yan-Bo Chen; Ci-Rong Lu; Yue-Jun Song; Xiao-Jun Li; Li-An Zhao (Tunnelling and Underground Space Technology, 2024)

Ent-atisane diterpenoids from Euphorbia wallichii and their anti-influenza A virus activity - Jie Zhang; Xiao-Jia Guo; Xiao-Juan Chen; Rong-Rong Zhang; Bai-Ping Ma; Zhong-Qiu Liu (Phytochemistry, 2024)

Identification of high oxygen-consuming substances in stormwater drainage systems illicitly connected with sewage system - Chen Xu; Zuxin Xu; Wenhai Chu; Shanshan Wu; Rong Xiao; Lei Su (Journal of Environmental Sciences, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Effect of topographic slope on the interaction between debris flows and riparian forests - Wen-rong Cui; Jian-gang Chen; Xiao-qing Chen; Dong-ri Song; Wan-yu Zhao; Ke Jin (Landslides, 2024)

Modification of polyacrylonitrile ultrafiltration membrane with acylase for enhanced biofouling control based on quorum quenching - Bingqian Hou; Xinyu Chen; Danni Wang; Ru Geng; Xiangtong Zhou; Xiang Xiao; Xinshan Rong; Zhiren Wu; Jing Wei (Journal of Water Process Engineering, 2024)

Damming-associated landscape change benefits a wind-dispersed pioneer plant species - Hang Ji; Yong-Rong He; Hong-Yue Li; Ling Lu; Jia-Hui Li; Jie Zou; Rong Wang; Jun-Yin Deng; Xiao-Yong Chen (New Forests, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Uranium speciation and distribution on the surface of Shewanella putrefaciens in the presence of inorganic phosphate and zero-valent iron under anaerobic conditions - Guo-Xiu Xuan; Guo-Hao Zhang; Wen-Cai Cheng; Chun-Yan Ma; Qing-Rong Li; En-Tong Liu; Wen-Ge He; Fa-Qin Dong; Xiao-An Li; Zheng-Guo Chen; Xiao-Qin Nie (Science of The Total Environment, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

The role of a small molecular dipole moment for efficient non-doped deep blue thermally activated delayed fluorescence emitters - Hong-Ji Tan; Jie-Rong Yu; Zhi-Zhong Lin; Guo-Xi Yang; Zhi-Qiang Long; Ying-Lan Deng; Ze-Lin Zhu; Xian-Kai Chen; Jing-Xin Jian; Qing-Xiao Tong; Chun-Sing Lee (Chemical Engineering Journal, 2024)

Exploring carbon content variation in microplastics sequestrated from seawater to sediment in the Haima cold seep area - Xiao-Nan Wu; Jing-Chun Feng; Xiao Chen; Can-Rong Li; Si Zhang (Journal of Hazardous Materials, 2024)

Multiscale computational fluid dynamics modelling of spatial ALD on porous li-ion battery electrodes - Zoushuang Li; Yuanxiao Chen; Yufeng Nie; Fan Yang; Xiao Liu; Yuan Gao; Bin Shan; Rong Chen (Chemical Engineering Journal, 2024)

B4C/Ce co-modified Ti/PbO2 dimensionally stable anode: Facile one-step electrodeposition preparation and highly efficient electrocatalytic degradation of tetracycline - Zeyi Wang; Rong Su; Maojie Zhao; Luyao Zhang; Lu Yang; Feng Xiao; Weishan Tang; Lichuan Chen; Ping He; Dingming Yang (Chemosphere, 2023)

Dynamic human exposure to airborne bacteria-associated antibiotic resistomes revealed by longitudinal personal monitoring data - Rong-min Zhang; Xin-lei Lian; Li-wei Shi; Liuyiqi Jiang; Shan-shan Chen; Wen-qing Haung; Jia-en Wu; Fei-jing Wu; Jian Sun; Xiao-ping Liao; Yun-xiao Chong; Ya-hong Liu; et al. (Science of The Total Environment, 2023)

Complete genome analysis of type strain of a novel bacterial family Temperatibacteraceae fam. nov., isolated from surface seawater - Jin-Cheng Rong; Lin-Lin Cui; Xiao-Chen Yang; Mao-Li Yi; Qi Zhao (Marine Genomics, 2023)

Chemical constituents of the leaves of Coriaria nepalensis and their chemotaxonomic significance - Min Tan; Xiao-Lan Chen; Xuan-Qin Chen; Rong-Tao Li; Zhi-Jun Zhang (Biochemical Systematics and Ecology, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

Efficient removal of uranium under strong acid based on charge separation and protonation coupled covalent organic frameworks - Shun-Mo Yi; Cheng-Rong Zhang; Xin Liu; Xiao-Juan Chen; Jia-Xin Qi; Cheng-Peng Niu; Jin-Lan Liu; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Positive relationships between species diversity and genetic diversity on a local scale at Mt. Wu Yi, China - Lei Xie; YueYao Feng; Rong Zhao; Ting Lv; NingJie Wang; Yao Li; Xiao Zheng; ShuiFei Chen; Hui Ding; YanMing Fang (Biodiversity and Conservation, 2023)

Three new hasubanan-type alkaloids from the Stephania longa - Rong-Xiao Lin; Lixia Fan; Xin Chen; Jundi Wu; Zheng Liu; Fang Liu; An-Ping Yang; Chenglai Xia; Hui Liu; Hong-Yuan Chen (Natural Product Research, 2023)

An integrative analysis of lipidomics and transcriptomics in various mouse brain regions in response to real-ambient PM2.5 exposure - Shuangjian Qin; Huixian Zeng; Qizhen Wu; Qingqing Li; Mohammed Zeeshan; Lizhu Ye; Yue Jiang; Rui Zhang; Xinhang Jiang; Miao Li; Rong Zhang; Wen Chen; et al. (Science of The Total Environment, 2023)

Neuroglobin Facilitates Neuronal Oxygenation through Tropic Migration under Hypoxia or Anemia in Rat: How Does the Brain Breathe? - Chun-Yang Li; Hai-Feng Jiang; Li Li; Xiao-Jing Lai; Qian-Rong Liu; Shang-Bin Yu; Cheng-La Yi; Xiao-Qian Chen (Neuroscience Bulletin, 2023)

Ultrasensitive detection and efficient removal of mercury ions based on covalent organic framework spheres with double active sites - Ke Xiao; Rong Zhu; Xiaohua Zhang; Cuicui Du; Jinhua Chen (Analytica Chimica Acta, 2023)

Effects of organic carbon/elemental carbon and particle size on inhalation bioaccessibility of particle-bound PAHs - Chun-Xue Tang; Ying Dong; Xiao-Yu Yuan; Rong Wang; Chen-Chou Wu; Lian-Jun Bao; Eddy Y. Zeng (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Multiomics reveals new biomarkers and mechanistic insights into the combined toxicity effects of 2,2′,4,4′,5,5′-hexachlorobiphenyl and atrazine exposures in MCF-7 cells - Yu-Shun Lu; Xing Wen; Ju Chen; Xiao-Rong He; Jiang Yu; Jing Qiu; Yong-Zhong Qian; Yan-Yang Xu (Environmental Pollution, 2023)

Prediction of daily PM2.5 and ozone based on high-density weather stations in China: Nonlinear effects of meteorology, human and ecosystem health risks - Lili Wang; Boya Liu; Rong Li; Xingfeng Chen; Lili Liu; Xiao Tang; Jingda Liu; Zhiheng Liao; Jinyuan Xin; Yuesi Wang; Bo Hu (Atmospheric Research, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Geochemical behaviors of uranium and thorium during weathering and pedogenesis of carbonate rock: constraint from their speciation - Qiang Ma; Bing-jie Zhou; Zhi-gang Feng; Xiao-long Wang; Rong Chen; Pei-shan Li; Chong Huang (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Faba bean above-ground biomass and bean yield estimation based on consumer-grade unmanned aerial vehicle RGB images and ensemble learning - Yishan Ji; Rong Liu; Yonggui Xiao; Yuxing Cui; Zhen Chen; Xuxiao Zong; Tao Yang (Precision Agriculture, 2023)

Clinical, Microbiological, and Molecular Characterization of Candida (Starmera) stellimalicola, a Rare Fungal Pathogen Causing Human Infections - Xin Fan; Rong-Chen Dai; Xiao-Feng Yan; Zhong-Shan Tong; Jie Gong (Mycopathologia, 2023)

Climatic seasonality challenges the stability of microbial‐driven deep soil carbon accumulation across China - Shuhai Wen; Jiaying Chen; Ziming Yang; Lei Deng; Jiao Feng; Wen Zhang; Xiao‐Min Zeng; Qiaoyun Huang; Manuel Delgado‐Baquerizo; Yu‐Rong Liu (Global Change Biology, 2023)
Microbial residues contribute to the long‐term stabilization of carbon in the entire soil profile, helping to regulate the climate of the planet; however, how sensitive these residues are to climatic seasonality remains virtually unknown, especially for deep soils across environmental gradients. Here, we investigated the changes of microbial residues along soil profiles (0–100 cm) from 44 typical ecosystems with a wide range of climates (~3100 km transects across China). Our results showed that microbial residues account for a larger portion of soil carbon in deeper (60–100 cm) vs. shallower (0–30 and 30–60 cm) soils. Moreover, we find that climate especially challenges the accumulation of microbial residues in deep soils, while soil properties and climate share their roles in controlling the residue accumulation in surface soils. Climatic seasonality, including positive correlations with summer precipitation and maximum monthly precipitation, as well as negative correlations with temperature annual range, are important factors explaining microbial residue accumulation in deep soils across China. In particular, summer precipitation is the key regulator of microbial‐driven carbon stability in deep soils, which has 37.2% of relative independent effects on deep‐soil microbial residue accumulation. Our work provides novel insights into the importance of climatic seasonality in driving the stabilization of microbial residues in deep soils, challenging the idea that deep soils as long‐term carbon reservoirs can buffer climate change.

A study of the lipid profile of Coix seeds from four areas based on untargeted lipidomics combined with multivariate algorithms to enable tracing of their origin - Peng Chen; Yabo Shi; Xiaoyan Xiao; Rong Xue; Yu Li; Lin Li; Chunqin Mao; Tulin Lu; Conglong Xu (Food Research International, 2023)

Inconsistent mercury records from terrestrial upland to coastal lowland across the Permian-Triassic transition - Jianbo Chen; Guangyi Sun; Binjian Lu; Rong-yao Ma; Zhuang Xiao; Yao-feng Cai; Hua Zhang; Shu-zhong Shen; Feifei Zhang; Zhuo Feng (Earth and Planetary Science Letters, 2023)

Constructing electron transport channels in FeSe2 microspheres by a facile strategy for superior long-life and ultrafast sodium-ion storage - Ming Xu; Yu Ma; Rong Liu; Huanhao Xiao; Liming Chen; Ziqiang Zhang; Lei Wang; Guohui Yuan (Chemical Engineering Journal, 2023)

Environmental polycyclic aromatic hydrocarbon exposure is associated with low back pain - Jiang Chen; Yangjie Liao; Mingjiang Luo; Siliang Tang; Jinshan Huang; Rong Chen; Zhihong Xiao (Environmental Geochemistry and Health, 2023)

The city-wide full-scale interactive application of sewage surveillance programme for assisting real-time COVID-19 pandemic control – A case study in Hong Kong - Wai-yin Ng; Wai Thoe; Rong Yang; Wai-ping Cheung; Che-kong Chen; King-ho To; Kan-ming Pak; Hon-wan Leung; Wai-kwan Lai; Tsz-kin Wong; Tat-kwong Lau; Ka-wing Au; et al. (Science of The Total Environment, 2023)

Ag@Bi5O7I nanoparticles deposited on Bi(OH)3 nanosheets for boosting photocatalytic antibacterial activity under visible light irradiation - Qinghan Chen; Li Wang; Dehui He; Bo Xiao; Xia Ran; Rong Li; Hong Xu; Jian Feng (Journal of Environmental Chemical Engineering, 2023)

Mesoporous zeolite Beta supported Ni nanoparticles for the catalytic hydroconversion of extraction portion from Jinjitan subbituminous coal to cycloalkanes - Juan Gao; Xian-Yong Wei; Yu-Hong Kang; Xiao-Qi Zhang; Ai-Min Wang; Xia-Long Li; Yong Gao; Guang-Hui Liu; Tao Chen; Yan-Jun Li; Xiang-Rong Ma; Jin-Jun Bai; et al. (Fuel, 2023)

Nitrogen doped titania stabilized Pt/C catalyst via selective atomic layer deposition for fuel cell oxygen reduction - Hang Liu; Qizi Lu; Yuxin Gao; Chaojun Huang; Aimin Zhang; Feng Liu; Henghui Xu; Xiao Liu; Bin Shan; Rong Chen (Chemical Engineering Journal, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Debris flow characteristics of the compound channels with vegetated floodplains - Wen-rong Cui; Jian-gang Chen; Xiao-qing Chen; Jin-bo Tang; Ke Jin (Science of The Total Environment, 2023)

Transcriptome sequencing and metabolite analysis reveal the single and combined effects of microplastics and di-(2-ethylhexyl) phthalate on Peneaus vannamei - Qiang-Qiang Shi; Xiao-Qian Zhang; Ze-Ming Zhang; Ning-Bo Wang; Hua Liu; Rong-Rong Zhang; Ai-Li Sun; Jiong Chen; Xi-Zhi Shi (Science of The Total Environment, 2023)

Disinfection byproducts in indoor swimming pool water: Detection and human lifetime health risk assessment - Di Zhang; Shengkun Dong; Li Chen; Rong Xiao; Wenhai Chu (Journal of Environmental Sciences, 2023)

Chemical constituents from the root bark of Morus alba and their chemotaxonomic significance - Xiao-Cong Liu; Xuan-Qin Chen; Rong-Tao Li; Zhi-Jun Zhang (Biochemical Systematics and Ecology, 2023)

Retraction Note: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2023)

Meal Skipping and Shorter Meal Intervals Are Associated with Increased Risk of All-Cause and Cardiovascular Disease Mortality among US Adults - Yangbo Sun; Shuang Rong; Buyun Liu; Yang Du; Yuxiao Wu; Liangkai Chen; Qian Xiao; Linda Snetselaar; Robert Wallace; Wei Bao (Journal of the Academy of Nutrition and Dietetics, 2023)

Flexible three-dimensional covalent organic frameworks for ultra-fast and selective extraction of uranium via hydrophilic engineering - Xiao-Juan Chen; Cheng-Rong Zhang; Xin Liu; Jia-Xin Qi; Wei Jiang; Shun-Mo Yi; Cheng-Peng Niu; Yuan-Jun Cai; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Exploring the potential anti-Alzheimer disease mechanisms of Alpiniae Oxyphyliae Fructus by network pharmacology study and molecular docking - Rong-Rong Zhen; Yan-Jie Qu; Li-Min Zhang; Chao Gu; Min-Rui Ding; Lei Chen; Xiao Peng; Bing Hu; Hong-Mei An (Metabolic Brain Disease, 2023)

Differences in lipid accumulation and mobilization in the hepatopancreas and ovary of female mud crab (Scylla paramamosain, Estampador, 1949) during ovarian development - Baojia Chen; Jia Zheng; Cuiying Chen; Kun Wu; Fan Lin; Lijun Ning; Hua Rong; Chuan Chen; Fei Xiao; Haotian Zhang; Xiaobo Wen (Aquaculture, 2023)

Four new glycosides from Gerbera piloselloides - Ha Gao; Chen-Xu Zhao; Xin-Yao Luo; Jing-Rong Li; Xiao-Chuan Ye; Tao Zhang; Zhong-Mei Zou (Phytochemistry Letters, 2023)

Coexistence of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) and IgA nephropathy - Qi Xiong; Wei Lin; Chanjuan Shen; Ting Meng; Rong Tang; Joshua D. Ooi; Peter J. Eggenhuizen; Jinbiao Chen; Wannian Nie; Xia Li; Qiaoling Zhou; Ping Xiao; et al. (Immunologic Research, 2023)

Evaluation of deep learning algorithms for landslide susceptibility mapping in an alpine-gorge area: a case study in Jiuzhaigou County - Di Wang; Rong-hao Yang; Xiao Wang; Shao-da Li; Jun-xiang Tan; Shi-qi Zhang; Shuo-you Wei; Zhang-ye Wu; Chao Chen; Xiao-xia Yang (Journal of Mountain Science, 2023)

Combined effect of Cu- and ZnO- NPs on antibiotic resistance genes in an estuarine water - Yu-ru Chen; Rong-rong Sha; Xiao-li Sun; Xing-pan Guo; Yi Yang (Frontiers in Marine Science, 2023)
Most studies of whether and how nanoparticles (NPs) affect antibiotic resistance genes (ARGs) focus on testing single NPs type. In this study, we determined the combined effect of Cu- and ZnO- NPs in the water samples collected from the Yangtze River Estuary and found the effect differs greatly from that produced by individual NPs. The results showed that the Cu- and ZnO- NPs co-exposure resulted in an enrichment of ARGs, whereas individual Cu- and ZnO- NPs exposure decreased the abundance of ARGs. Furthermore, the co-exposure of Cu- and ZnO- NPs induced obvious changes in the microbial communities compared to the control communities. Redundancy analysis suggested that the microbial community contributed the most (43.5%) to the ARG profiles, followed by dissolved metal ions (25.7%), MRGs, (19.4%), and MGEs (4.4%). Network analysis found several potential hosts (such as Mycobacterium and Escherichia coli ) and implied the extent of the risk of ARG transmission into various environmental niches by these common microbes.

Nondestructive and rapid method for sex identification of the tropical sea cucumber Holothuria scabra by anal swab sampling - Zixuan E; Chuhang Cheng; Feifei Wu; Chunhua Ren; Rong Chen; Yingzhu Rao; Bo Ma; Xiao Jiang; Peng Luo; Xiaomin Li; Xin Zhang; Fajun Jiang; et al. (Aquaculture, 2023)

Zinc finger protein 671 has a cancer-inhibiting function in colorectal carcinoma via the deactivation of Notch signaling - Yan Wang; Fen-rong Chen; Chong-cao Wei; Lin-lang Sun; Chen-yu Liu; Long-bao Yang; Xiao-yan Guo (Toxicology and Applied Pharmacology, 2023)

Zero-valent iron boosts nitrate-to-ammonia bioconversion via extracellular electron donation and reduction pathway complementation - Xue Li; Jie Li; Xiao-Rong Yu; Yong-Kun Zhu; Hou-Qi Liu; Lin Chen; Jing Wu; Xian-Zhong Fu; Shuo Cui; Tian-Yin Huang; Ru-Quan Ye; Wen-Wei Li (Resources, Conservation and Recycling, 2023)

Evolving a high-performance bio-imaging tool derived from a compact fluorophore as well as creating a reaction-based fluorescent probe for precise determination of Ag+ - Zi Yi Xu; Xiao Hu Wang; Sha Li Huang; Jing Rong Chen; Hong Qun Luo; Nian Bing Li (Chemical Engineering Journal, 2023)

Poly(ionic liquid) boosts overall performance of electrocatalytic reduction of low concentration of CO gas - Guo-Yi Duan; Xiao-Qiang Li; Jun-Wu Chen; Guang-Rong Ding; Peng-Xin Guan; Bao-Hua Xu (Chemical Engineering Journal, 2023)

Exposure–response relationship between temperature, relative humidity, and varicella: a multicity study in South China - Yihan Li; Jialing Li; Zhihua Zhu; Weilin Zeng; Qi Zhu; Zuhua Rong; Jianxiong Hu; Xing Li; Guanhao He; Jianguo Zhao; Lihua Yin; Yi Quan; et al. (Environmental Science and Pollution Research, 2023)

Physiological and transcriptome analysis of Mytilus coruscus in response to Prorocentrum lima and microplastics - Xiao-wen Tang; Rong Yu; Mei-hua Fan; Zhi Yang; Zhi Liao; Zong-xin Yang; Chen-ying Xie; Yu-kun Xuan; Jian-xin Wang; Xiao-lin Zhang; Xiao-jun Yan (Frontiers in Marine Science, 2022)
Nowadays, diarrheic shellfish toxicity (DSP) toxin and microplastics (MPs) are commonly found in coastal waters worldwide. Due to their widespread use, their persistence and toxicity, they may induce adverse effects on Mytilus coruscus . However, the underlying toxic mechanisms of DSP and MPs on M. coruscus remain unclear. This study explored the physiological index and transcriptome change of the digestive gland of adult M. coruscus exposed for 3 days to polystyrene (PS) MPs (0.2 mg/L, 90-100 μm) and Prorocentrum lima alone or in combination. The results showed that the CAT activity and MDA content significantly increased, respiration rate and feeding rate significantly decreased. The combination of MPs and P. lima caused more structural damage to the rough surface endoplasmic reticulum and mitochondria in the digestive glands of M. coruscus . The transcriptome analysis showed that 485 and 220 genes were up- and down-regulated, respectively, after exposure to P. lima ; 1,989 up-regulated DEGs and 1,098 down-regulated DEGs were identified after exposure to MP treatment, and 1,004 up-regulated DEGs and 664 down-regulated DEGs were identified after exposure to the combination of P. lima and MPs. The DEGs were mainly enriched in the lysosome, mRNA surveillance pathway, carbon metabolism, the mTOR signaling pathway, the complement and coagulation cascades, and the TNF signaling pathway. The MP, P. lima exposure mainly induced the expression of RNA-binding protein musashi, serine/arginine repetitive matrix protein 1, low affinity immunoglobulin epsilon Fc receptor, toll-like receptor 2, caspase 7, calmodulin, E3 ubiquitin-protein ligase, serine/threonine-protein kinase PRP4, glutathione S-transferase, and heat shock 70 kDa protein. MPs and P. lima poison mainly influence the expression of RNA transport, immune related gene, apoptosis, signal related gene, and antioxidant gene change. The combination of MPs and P. lima has a synergistic toxic effect. This study provides a new insights into its physiological and molecular responses of M. coruscus to MPs and P. lima toxic exposure.

Establishment of a novel myocarditis mouse model based on cyclosporine A - Tian Hao Zhao; Yi Xuan Jiang; Kai Qin Chen; Dan Qiu; Yan Zhe Xu; Chun Ye; Ting Ren; Bo Zhang; Bin Dai; Jue Hu; Jun Lu; Fang Liang Zhou; et al. (Genes & Genomics, 2022)

Infestation and distribution of chigger mites on Confucian white-bellied rat (Niviventer confucianus) in Southwest China - Yan-Ling Chen; Xian-Guo Guo; Wen-Yu Song; Tian-Guang Ren; Lei Zhang; Rong Fan; Cheng-Fu Zhao; Zhi-Wei Zhang; Wen-Ge Dong; Xiao-Bin Huang (Biologia, 2022)

A study on the enrichment mechanism of three nitrophenol isomers in environmental water samples by charge transfer supramolecular-mediated hollow fiber liquid-phase microextraction - Zhao-hui Wang; Dou-dou Xu; Xiao-hong Bai; Shuang Hu; Rong-rong Xing; Xuan Chen (Environmental Science and Pollution Research, 2022)

MoS2 boosts the Fe2+/PMS process for carbamazepine degradation - Huan Peng; Rong Chen; Ningyao Tao; Yangyi Xiao; Chenxing Li; Tuqiao Zhang; Miaomiao Ye (Environmental Science and Pollution Research, 2022)

Hasubanan alkaloids with anti-inflammatory activity from Stephania longa - Hui Liu; Wan-Qin Liao; Rong-Xiao Lin; Lixia Fan; Jinyan Sun; Hong-Yuan Chen; Fang Liu; An-Ping Yang (Natural Product Research, 2022)

Impact of heat stress on milk yield, antioxidative levels, and serum metabolites in primiparous and multiparous Holstein cows - Xue Chen; Jia Nan Dong; Ji Ye Rong; Jun Xiao; Wei Zhao; Natnael D. Aschalew; Xue Feng Zhang; Tao Wang; Gui Xin Qin; Zhe Sun; Yu Guo Zhen (Tropical Animal Health and Production, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Monascuslactams A–D, cytotoxic γ-lactams from marine fungus Monascus albidus BB3 - Qi Guo; Xiao-Ming Dai; Wen-Jian Lan; Liu-Ping Chen; Chi-Keung Lam; Gong-Kan Feng; Rong Deng; Xiao-Feng Zhu; Hou-Jin Li (Natural Product Research, 2022)

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Neoflavonoids from the heartwood of Dalbergia melanoxylon - Meng-fei Wang; Guang-qiang Ma; Feng Shao; Rong-hua Liu; Lan-ying Chen; Yang Liu; Li Yang; Xiao-wei Meng (Natural Product Research, 2022)

One new α , β -unsaturated 7-ketone sterol from the mangrove-derived fungus Phomopsis sp.MGF222 - Xiao-Chen Zhu; Guo-Lei Huang; Rong-Qing Mei; Bin Wang; Xue-Ping Sun; You-Ping Luo; Jing Xu; Cai-Juan Zheng (Natural Product Research, 2021)

Emerging role of air pollution in chronic kidney disease - Yue Chen; Fan Cao; Jian-Ping Xiao; Xin-Yu Fang; Xue-Rong Wang; Li-Hong Ding; De-Guang Wang; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

The effectiveness of extended binding affinity of prophage lysin PlyARI against Streptococcus suis infection - Yuyi Xiao; Rong Chen; Min Li; Zitai Qi; Yanfei Yu; Zihao Pan; Huochun Yao; Zhixin Feng; Wei Zhang (Archives of Microbiology, 2021)

Source–sink dynamics assists the maintenance of a pollinating wasp - Xin Tong; Yuan‐Yuan Ding; Jun‐Yin Deng; Rong Wang; Xiao‐Yong Chen (Molecular Ecology, 2021)
Dispersal that unites spatially subdivided populations into a metapopulation with source–sink dynamics is crucial for species persistence in fragmented landscapes. Understanding such dynamics for pollinators is particularly urgent owing to the ongoing global pollination crisis. Here, we investigated the population structure and source–sink dynamics of a pollinating wasp ( Wiebesia sp. 3) of Ficus pumila in the Zhoushan Archipelago of China. We found significant asymmetry in the pairwise migrant numbers for 22 of 28 cases on the historical timescale, but only two on the contemporary timescale. Despite a small population size, the sole island not colonized by a superior competitor wasp ( Wiebesia sp. 1) consistently behaved as a net exporter of migrants, supplying large sinks. Comparable levels of genetic diversity, with few private alleles and low genetic differentiation (total F st : 0.03; pairwise F st : 0.0005–0.0791), were revealed among all the islands. There was a significant isolation‐by‐distance pattern caused mainly by migration between the competition‐free island and other islands, otherwise the pattern was negligible. The clustering analysis failed to detect multiple gene pools for the whole region. Thus, the sinks were most probably organized into a patchy population. Moreover, the estimates of effective population sizes were comparable between the two timescales. Thus the source–sink dynamics embedded within a well‐connected population network may allow Wiebesia sp. 3 to persist at a competitive disadvantage. This study provides evidence that metapopulations in the real world may be complicated and changeable over time, highlighting the necessity to study such metapopulations in detail.

Dual effects of insect fecundity overdispersion on the Wolbachia establishment and the implications for epidemic biocontrol - Xin Tong; Stephen G. Compton; Jing Jiao; Yan Chen; Yuan-Yuan Ding; Rong Wang; Xiao-Yong Chen (Journal of Pest Science, 2021)

Effect of C/N Ratio on Nitrogen Removal of A/O-MBBR Process for Treating Mariculture Wastewater - Xi Chen; Zhuangzhuang Xiang; Xiao Huang; Huimin Rong; Jie Bai; Yangguo Zhao (Journal of Ocean University of China, 2021)

Genotypic variation in nitrogen utilization efficiency in oilseed rape is related to the coordination of leaf senescence and root N uptake during reproductive stage - Huiying He; Yuyu Xie; Anyu Zhao; Wencong Hu; Xiao Guo; Anthony J. Miller; Xiaoming Wu; Biyun Chen; Rong Zhang; Hui Tian; Yajun Gao (Plant and Soil, 2021)

Neuroprotective Effect of Phthalide Derivative CD21 against Ischemic Brain Injury:Involvement of MSR1 Mediated DAMP peroxiredoxin1 Clearance and TLR4 Signaling Inhibition - Xiao Zou; Xiao-Jia Yang; Yu-Miao Gan; Dong-Ling Liu; Chu Chen; Wei Duan; Jun-Rong Du (Journal of Neuroimmune Pharmacology, 2021)

A Eu(III)-based Metal Organic Framework: Selective Sensing of Picric Acid and Nursing Application Values On the Cerebral Edema Induced by Cerebral Hemorrhage Via Reducing the Coagulation Factor II Activity - Xiao-Chang Chen; Feng Xi; Rong Liu; Jia-Wen Zhou (Journal of Fluorescence, 2021)

Correlation of exosomal microRNA clusters with bone metastasis in non-small cell lung cancer - Xiao-Rong Yang; Can Pi; Ruoying Yu; Xiao-Jun Fan; Xiao-Xiao Peng; Xu-Chao Zhang; Zhi-Hong Chen; Xue Wu; Yang Shao; Yi-Long Wu; Qing Zhou (Clinical & Experimental Metastasis, 2021)
20–40% of lung cancer patients develop bone metastasis (BM) with significantly decreased overall survival. Currently, BM is mainly diagnosed by computerized tomography (CT) scan or magnetic resonance imaging (MRI) when symptom develops. Novel biomarkers with higher prediction value of BM are needed. Plasma-derived exosomal microRNAs had been isolated and sequenced of total 30 non-small cell lung cancer (NSCLC) patients including 16 with bone metastasis and 14 without bone metastasis. Hierarchical clustering based on the total miRNA profile can clearly separate cancer patients and healthy individuals (H), but not patients with (BM +) or without (BM−) BM. Weight Co-expression network of miRNAs (WGCNA) analyses identified three consensus clusters (A, B, C) of highly correlated miRNAs, among which cluster B (144 miRNAs) showed significantly differential expression in lung cancer patients, especially in BM + group. Pathway analysis of cluster B miRNAs revealed enrichment in metabolic pathways that may involve in preconditioning of the metastatic niche. Three differentially expressed miRNAs between BM + and BM− patients within cluster B were identified as miR-574-5p, a suppressor of Wnt/β-catenin pathway, was down-regulated, while miR-328-3p and miR-423-3p, two activators of the same pathway, were up-regulated in BM + patients. Cluster A miRNAs (n = 49) also showed trend of upregulation in BM + patients. Interestingly, pathway analysis indicated that 43 of them are associated with chromosome14, which has been suggested to promote epithelial-mesenchymal transition (EMT) and bone metastasis.

Larger regional volume of the thalamus in diarrhea-predominant irritable bowel syndrome: a cross-sectional study - Cui Ping Mao; Fen Rong Chen; Hong Hong Sun; Mei Juan Shi; Hua Juan Yang; Xiao Hui Li; Dun Ding (Brain Imaging and Behavior, 2020)

Tectochrysin increases stress resistance and extends the lifespan of Caenorhabditis elegans via FOXO/DAF-16 - Min Lu; Lin Tan; Xiao-Gang Zhou; Zhong-Lin Yang; Qing Zhu; Jian-Ning Chen; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2020)

NLRP6 contributes to inflammation and brain injury following intracerebral haemorrhage by activating autophagy - Han Xiao; Hui Chen; Rong Jiang; Li Zhang; Lu Wang; Hui Gan; Ning Jiang; Jing Zhao; Xuan Zhai; Ping Liang (Journal of Molecular Medicine, 2020)

Habitat fragmentation changes top‐down and bottom‐up controls of food webs - Rong Wang; Xin Zhang; Yi‐Su Shi; Yuan‐Yuan Li; Jianguo Wu; Fangliang He; Xiao‐Yong Chen (Ecology, 2020)
Top‐down and bottom‐up controls regulate the structure and stability of ecosystems, but their relative roles in terrestrial systems have been debated. Here we studied a hydro‐inundated land‐bridge system in subtropical China and tested the relative importance of these two controls in determining the rodent‐mediated regeneration of a locally dominant tree species. Our results showed that both controls operated in terrestrial habitats and that their relative importance switched as habitat size changed. Habitat loss initially removed predators of rodents that released rodent populations and triggered massive seed predation (top‐down control), leading to reduced seedling establishment. A further reduction in habitat size led to decrease in rodent population that was supposed to increase seedling survival of the tree species, but the decline in habitat size deteriorated the abiotic environments (bottom‐up control) that severely prevented seedling recruitment. As the ongoing global land use change is creating increasing number of small‐sized forest fragments, our findings provide novel insights into the restoration of seriously fragmented forests.

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Disruption of functional connectivity among subcortical arousal system and cortical networks in temporal lobe epilepsy - Rong Li; Chongyu Hu; Liangcheng Wang; Ding Liu; Dingyang Liu; Wei Liao; Bo Xiao; Huafu Chen; Li Feng (Brain Imaging and Behavior, 2020)

Interaction between Translocation-associated membrane protein 1 and σC protein of novel duck reovirus controls virus infectivity - Rong Xiao; Xiaoyun Mi; Jiahui Sun; Mingyang Ding; Chuanfeng Li; Jie Zhu; Guangqing Liu; Wenge Ma; Hailong Zhou; Zongyan Chen (Virus Genes, 2020)

Simulating Spatial Variation of Soil Carbon Content in the Yellow River Delta: Comparative Analysis of Two Artificial Neural Network Models - Chen Wang; Yuan Cui; Ziwen Ma; Yutong Guo; Qian Wang; Yujiao Xiu; Rong Xiao; Mingxiang Zhang (Wetlands, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Elevated Hs-CRP Levels Are Associated with Higher Risk of Intracranial Arterial Stenosis - Bing-Jie Su; Yi Dong; Chen-Chen Tan; Xiao-He Hou; Wei Xu; Fu-Rong Sun; Mei Cui; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Sol-gel hydrothermal synthesis of nano crystalline silicotitanate and its strontium and cesium adsorption - Rong Wang; Zhenggang Luo; Qiuxia Tan; Rui Wang; Shuyuan Chen; Jiancheng Shu; Mengjun Chen; Zhengxue Xiao (Environmental Science and Pollution Research, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

RETRACTED ARTICLE: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2020)

De novo assembly and transcriptome analysis of differentially expressed genes relevant to variegation in hawthorn flowers - Wei Ji; Wei Zhao; Rong-Chen Liu; Xiao-Bo Jiao; Kai Han; Zhong-Yi Yang; Mei-Ying Gao; Rui Ren; Xiu-Juan Fan; Ming-Xia Yang (Plant Biotechnology Reports, 2019)

Quantifying Flood Frequency Modification Caused by Multi-Reservoir Regulation - Yi-han Tang; Jie-feng Wu; Pei-yi Li; Li-juan Zhang; Xiao-hong Chen; Kai-rong Lin (Water Resources Management, 2019)

Effects of nutrient addition on foliar phosphorus fractions and their resorption in different-aged leaves of Chinese fir in subtropical China - Fang-Chao Wang; Xiang-Min Fang; G. Geoff Wang; Rong Mao; Xiao-Fan Lin; Huimin Wang; Fu-Sheng Chen (Plant and Soil, 2019)

Nitrogen use-inefficient oilseed rape genotypes exhibit stronger growth potency during the vegetative growth stage - Xiao Guo; Huiying He; Rong An; Yuying Zhang; Rui Yang; Lanqin Cao; Xiaoming Wu; Biyun Chen; Hui Tian; Yajun Gao (Acta Physiologiae Plantarum, 2019)

Recent advances in carbohydrate-based cancer vaccines - Ke-Tao Jin; Huan-Rong Lan; Xiao-Yi Chen; Shi-Bing Wang; Xiao-Jiang Ying; Yan Lin; Xiao-Zhou Mou (Biotechnology Letters, 2019)

First report of isolation and complete genome of Vibrio rotiferianus strain SSVR1601 from cage‐cultured black rockfish ( Sebastes schlegelii ) associated with skin ulcer - Zheng Zhang; Yong‐xiang Yu; Yong Jiang; Yin‐geng Wang; Mei‐jie Liao; Xiao‐jun Rong; Kai Wang; Hao Zhang; Jing Chen (Journal of Fish Diseases, 2019)
Vibrio rotiferianus is an important marine pathogen of various aquatic organisms and can be found widely distributed in the marine environment. To further characterize this pathogen, the pathogenic properties and genome of V. rotiferianus SSVR1601 isolated from Sebastes schlegelii with skin ulcer were analysed. SSVR1601 was shown to be short rod‐shaped cell with a single polar flagellum. Different degrees of pathological changes in fish kidney, intestine, gills and liver were observed after SSVR1601 challenge. The SSVR1601 genome consists of two chromosomes and two plasmids with a total of 5,717,113 bp, 42.04%–44.93% GC content, 5,269 predicted CDSs, 134 tRNAs and 40 rRNAs. The common virulence factors including OMPs, haemolysin, flagellin, DNase, entF , algU , tcpI , acfB and rfaD were found in strain SSVR1601. Furthermore, factors responsible for iron uptake ( fur , fepC and ccmC ) and types II, IV and VI secretion systems were detected, which are likely responsible for the pathogenicity of SSVR1601. The antimicrobial resistance genes, bacA , tet34 and norM, were detected based on Antibiotic Resistance Genes Database. The phylogenetic analysis revealed SSVR1601 to be most closely related to V. rotiferianus strains CAIM577 and B64D1.

Incidence and clinical correlates of anger attacks in Chinese patients with obsessive-compulsive disorder - Ying-ying Zhang; Heng-fen Gong; Xiao-li Zhang; Wen-juan Liu; Hai-yan Jin; Fang Fang; Sophie Schneider; Elizabeth McIngvale; Chen-cheng Zhang; Wayne K. Goodman; Xi-rong Sun; Eric A. Storch (Journal of Zhejiang University-SCIENCE B, 2019)

Relationship between polymorphisms of the lipid metabolism-related gene PLA2G16 and risk of colorectal cancer in the Chinese population - Xiao-Nv Xie; Jing Yu; Li-Hua Zhang; Zhi-Ying Luo; Dong-Sheng Ouyang; Ling-Jie Zheng; Chun-Yang Wang; Li Yang; Ling Chen; Zhi-Rong Tan (Functional & Integrative Genomics, 2019)

Insights into the effect of chemical treatment on the physicochemical characteristics and adsorption behavior of pig manure-derived biochars - Rong-Zhong Wang; Dan-Lian Huang; Chen Zhang; Yun-Guo Liu; Guang-Ming Zeng; Cui Lai; Xiao-Min Gong; Min Cheng; Jia Wan; Qing Zhang (Environmental Science and Pollution Research, 2019)

The Influence of Cellulosic Polymer’s Variables on Dissolution/Solubility of Amorphous Felodipine and Crystallization Inhibition from a Supersaturated State - Nian-Qiu Shi; Ying Jin; Yong Zhang; Xiao-Xia Che; Xiao Xiao; Gui-Hua Cui; Yu-Zhou Chen; Bo Feng; Zheng-Qiang Li; Xian-Rong Qi (AAPS PharmSciTech, 2019)

Molecular and morphological data reveals new insights into genetic diversity and population structure of Chinese cherry (Prunus pseudocerasus Lindl.) landraces - Tao Chen; Yue-yang Hu; Qing Chen; Yan Wang; Jing Zhang; Hao-ru Tang; Xiao-rong Wang (Genetic Resources and Crop Evolution, 2018)

miR-153 inhibits the migration and the tube formation of endothelial cells by blocking the paracrine of angiopoietin 1 in breast cancer cells - Huichun Liang; Fei Ge; Yuhui Xu; Ji Xiao; Zhongmei Zhou; Rong Liu; Ceshi Chen (Angiogenesis, 2018)

Identification and genetic mapping for rht-DM, a dominant dwarfing gene in mutant semi-dwarf maize using QTL-seq approach - Qian Chen; Jun Song; Wen-Ping Du; Li-Yuan Xu; Yun Jiang; Jie Zhang; Xiao-Li Xiang; Gui-Rong Yu (Genes & Genomics, 2018)

Fisheries in Chinese seas: What can we learn from controversial official fisheries statistics? - Bin Kang; Min Liu; Xiao-Xia Huang; Jun Li; Yun-Rong Yan; Chiao-Chuan Han; Shao-Bo Chen (Reviews in Fish Biology and Fisheries, 2018)

The complete mitochondrial genome sequence of Anthracoceros coronatus (Bucerotiformes: Bucerotidae) - Rong Li; Yanyan Chen; Haiya Yan; Chunqing Li; Heng Xiao; Shanyuan Chen (Conservation Genetics Resources, 2018)

Knockdown expression of IL-10Rα gene inhibits PRRSV replication and elevates immune responses in PBMCs of Tibetan pig in vitro - Yihui Chen; Ye Wang; Kai Zeng; Yun-feng Lei; Xiao-hui Chen; San-cheng Ying; Xue-Bin Lv; Zezhou Wang; Rong Gao (Veterinary Research Communications, 2018)

Discovery of a novel multifunctional carbazole–aminoquinoline dimer for Alzheimer's disease: copper selective chelation, anti-amyloid aggregation, and neuroprotection - Xiao Zhang; Ying Wang; Sheng-nan Wang; Qiu-he Chen; Ya-lin Tu; Xiao-hong Yang; Jing-kao Chen; Jin-wu Yan; Rong-biao Pi; Yan Wang (Medicinal Chemistry Research, 2018)

Anti-oral common pathogenic bacterial active acetylenic acids from Thesium chinense Turcz - Chang Liu; Xiao-Tian Li; Rong-Rong Cheng; Zhu-Zhen Han; Li Yang; Zhong-Chen Song; Zheng-Tao Wang (Journal of Natural Medicines, 2018)

Uhrf2 deletion impairs the formation of hippocampus-dependent memory by changing the structure of the dentate gyrus - Xiao-Rong Chen; Shi-Cheng Sun; Shuai-Wen Teng; Liang Li; Yi-Fan Bie; Hui Yu; Da-Li Li; Zhe-Yu Chen; Yue Wang (Brain Structure and Function, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Bioorganic fertilizer maintains a more stable soil microbiome than chemical fertilizer for monocropping - Feng Cai; Guan Pang; Rui-Xia Li; Rong Li; Xiao-Long Gu; Qi-Rong Shen; Wei Chen (Biology and Fertility of Soils, 2017)

Efficacy and safety of probiotic-supplemented triple therapy for eradication of Helicobacter pylori in children: a systematic review and network meta-analysis - Jue-Rong Feng; Fan Wang; Xiao Qiu; Lynne V. McFarland; Peng-Fei Chen; Rui Zhou; Jing Liu; Qiu Zhao; Jin Li (European Journal of Clinical Pharmacology, 2017)

Effects of potassium deficiency on root morphology, ultrastructure and antioxidant enzyme system in sweet potato (Ipomoea batatas [L.] Lam.) during early growth - Ming Liu; Ai-Jun Zhang; Xiao-Guang Chen; Rong Jin; Hong-Min Li; Zhong-Hou Tang (Acta Physiologiae Plantarum, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

Spatial distribution of turbulent mixing in the upper ocean of the South China Sea - Xiao-Dong Shang; Chang-Rong Liang; Gui-Ying Chen (Ocean Science, 2017)
The spatial distribution of the dissipation rate (ε) and diapycnal diffusivity (κ) in the upper ocean of the South China Sea (SCS) is presented from a measurement program conducted from 26 April to 23 May 2010. In the vertical distribution, the dissipation rates below the surface mixed layer were predominantly high in the thermocline where shear and stratification were strong. In the regional distribution, high dissipation rates and diapycnal diffusivities were observed in the region to the west of the Luzon Strait, with an average dissipation rate and diapycnal diffusivity of 8.3 × 10−9 W kg−1 and 2.7 × 10−5 m2 s−1, respectively, almost 1 order of magnitude higher than those in the central and southern SCS. In the region to the west of the Luzon Strait, the water column was characterized by strong shear and weak stratification. Elevated dissipation rates (ε > 10−7 W kg−1) and diapycnal diffusivities (κ > 10−4 m2 s−1), induced by shear instability, occurred in the water column. In the central and southern SCS, the water column was characterized by strong stratification and weak shear and the turbulent mixing was weak. Internal waves and internal tides generated near the Luzon Strait are expected to make a dominant contribution to the strong turbulent mixing and shear in the region to the west of the Luzon Strait. The observed dissipation rates were found to scale positively with the shear and stratification, which were consistent with the MacKinnon–Gregg model used for the continental shelf but different from the Gregg–Henyey scaling used for the open ocean.

Involvement of the miR-462/731 cluster in hypoxia response in Megalobrama amblycephala - Cui-Hong Huang; Nan Chen; Chun-Xiao Huang; Bao Zhang; Meng Wu; Lei He; Hong Liu; Rong Tang; Wei-Min Wang; Huan-Ling Wang (Fish Physiology and Biochemistry, 2017)

Observations of the turbulent kinetic energy dissipation rate in the upper central South China Sea - Chang-Rong Liang; Gui-Ying Chen; Xiao-Dong Shang (Ocean Dynamics, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

MEF2D Mediates the Neuroprotective Effect of Methylene Blue Against Glutamate-Induced Oxidative Damage in HT22 Hippocampal Cells - Zi-wei Chen; Anmin Liu; Qingyu Liu; Jingkao Chen; Wen-ming Li; Xiao-juan Chao; Qian Yang; Pei-qing Liu; Zi-xu Mao; Rong-biao Pi (Molecular Neurobiology, 2017)

Synthesis and evaluation of multifunctional ferulic and caffeic acid dimers for Alzheimer’s disease - Xi-xin He; Xiao-hong Yang; Rui-ying Ou; Ying Ouyang; Sheng-nan Wang; Zi-wei Chen; Shi-jun Wen; Rong-biao Pi (Natural Product Research, 2017)

Identification of a New Rice Low-Tiller Mutant and Association Analyses Based on the SLAF-seq Method - Yan Li; Xiao-Fang Zeng; Yi-Chen Zhao; Jian-Rong Li; De-Gang Zhao (Plant Molecular Biology Reporter, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Trichoderma harzianum-induced resistance against Fusarium oxysporum involves regulation of nuclear DNA content, cell viability and cell cycle-related genes expression in cucumber roots - Shuang-Chen Chen; Hong-Jiao Zhao; Zhong-Hong Wang; Cai-Xia Zheng; Pu-Yan Zhao; Zhi-Hua Guan; Hai-Yang Qin; Ai-Rong Liu; Xiao-Min Lin; Golam-Jalal Ahammed (European Journal of Plant Pathology, 2017)

EGFL7-overexpressing epidermal stem cells promotes fibroblast proliferation and migration via mediating cell adhesion and strengthening cytoskeleton - Rong-Hua Yang; Shao-Hai Qi; Shu-Bin Ruan; Ze-Peng Lin; Yan Lin; Feng-Gang Zhang; Xiao-Dong Chen; Ju-Lin Xie (Molecular and Cellular Biochemistry, 2016)

A study on the Dushiling tungsten-copper deposit in the Miao’ershan-Yuechengling area, Northern Guangxi, China: Implications for variations in the mineralization of multi-aged composite granite plutons - WenDi Chen; WenLan Zhang; RuCheng Wang; ZhuYin Chu; Rong Xiao; Di Zhang; XuDong Che (Science China Earth Sciences, 2016)

Antidepressant-like effects of standardized gypenosides: involvement of brain-derived neurotrophic factor signaling in hippocampus - Rong-Hao Mu; Xiao-Yan Fang; Shuang-Shuang Wang; Cheng-Fu Li; Shao-Mei Chen; Xue-Mei Chen; Qing Liu; Yu-Cheng Li; Li-Tao Yi (Psychopharmacology, 2016)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

Evaluation of the major royal jelly proteins as an alternative to fetal bovine serum in culturing human cell lines - Di Chen; Xiao-xuan Xin; Hao-cheng Qian; Zhang-yin Yu; Li-rong Shen (Journal of Zhejiang University-SCIENCE B, 2016)

Genetic Diversity and Population Structure Patterns in Chinese Cherry (Prunus pseudocerasus Lindl) Landraces - Tao Chen; Xiao-jiao Huang; Jing Zhang; Qing Chen; Yin Liu; Hao-ru Tang; Dong-ming Pan; Xiao-rong Wang (Plant Molecular Biology Reporter, 2016)

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Preparation of Bacterial Cellulose/Inorganic Gel of Bentonite Composite by In Situ Modification - Bo Wang; Gao-xiang Qi; Chao Huang; Xiao-Yan Yang; Hai-Rong Zhang; Jun Luo; Xue-Fang Chen; Lian Xiong; Xin-De Chen (Indian Journal of Microbiology, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Lentibacillus amyloliquefaciens sp. nov., a halophilic bacterium isolated from saline sediment sample - Jing-Li Wang; Ke-Dong Ma; Yan-Wei Wang; Hui-Min Wang; Yan-Bin Li; Shan Zhou; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Ming-Xiong He; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2016)

Comparison of seven colchicine-induced tetraploid clones with their original diploid clones in purple coneflower (Echinacea purpurea L.) - Rong Chen; Wei-zhen Jiang; Qing-ling Li; Xin-lian Li; Xiao-lu Chen; Yue-sheng Yang; Hong Wu (Euphytica, 2016)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

Rab from the white shrimp Litopenaeus vannamei: characterization and its regulation upon environmental stress - Lei Wang; Xiao-Rong Wang; Jin Liu; Chu-Xian Chen; Yuan Liu; Wei-Na Wang (Ecotoxicology, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Paenibacillus populi sp. nov., a novel bacterium isolated from the rhizosphere of Populus alba - Tong-Yan Han; Xiao-Mei Tong; Yan-Wei Wang; Hui-Min Wang; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2015)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

Effects of glucose, insulin and triiodothyroxine on leptin and leptin receptor expression and the effects of leptin on activities of enzymes related to glucose metabolism in grass carp (Ctenopharyngodon idella) hepatocytes - Rong-Hua Lu; Yi Zhou; Xiao-Chen Yuan; Xu-Fang Liang; Liu Fang; Xiao-Li Bai; Min Wang; Yu-Hua Zhao (Fish Physiology and Biochemistry, 2015)

Genetic diversity revealed by morphological traits and ISSR markers in 48 Okras (Abelmoschus escullentus L.) - Cong-Ying Yuan; Ping Wang; Pang-Pang Chen; Wen-Jun Xiao; Cheng Zhang; Shuai Hu; Ping Zhou; Hong-Ping Chang; Zhuang He; Rong Hu; Xiu-Tao Lu; Jia-Zhuo Ye; et al. (Physiology and Molecular Biology of Plants, 2015)

Spiculisporic acid analogues of the marine-derived fungus, Aspergillus candidus strain HDf2, and their antibacterial activity - Rong Wang; Zhi Kai Guo; Xiang Min Li; Fu Xiao Chen; Xia Fei Zhan; Ming Hui Shen (Antonie van Leeuwenhoek, 2015)

Paenibacillus vini sp. nov., isolated from alcohol fermentation pit mud in Sichuan Province, China - Xiao-Rong Chen; Cheng-Bin Shao; Yan-Wei Wang; Ming-Xiong He; Ke-Dong Ma; Hui-Min Wang; De-Long Kong; Xiang Guo; Yi-Qing Zhou; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2015)

Immunosuppressive Effect of Hypodermin C on Complement Component 3 In Vitro - An-Kang Hu; Ren-Jin Chen; Xiao-Rong Zhu; Jian-Hong Gu; Zong-Ping Liu (Cell Biochemistry and Biophysics, 2015)

Association analyses of FGFR2 gene polymorphisms with femoral neck bone mineral density in Chinese Han population - Shan-Shan Dong; Tie-Lin Yang; Han Yan; Zheng-Qin Rong; Jia-Bin Chen; Ruo-Han Hao; Xiao-Feng Chen; Yan Guo (Molecular Genetics and Genomics, 2015)

Expression and clinical role of TCTP in epithelial ovarian cancer - Chen Chen; Yan Deng; Minhui Hua; Qinghua Xi; Rong Liu; Shuyun Yang; Jian Liu; Jianxin Zhong; Meilan Tang; Shumin Lu; Zhimei Zhang; Xiao Min; et al. (Journal of Molecular Histology, 2015)

Identification of microRNAs and their target genes in Alport syndrome using deep sequencing of iPSCs samples - Wen-biao Chen; Jian-rong Huang; Xiang-qi Yu; Xiao-cong Lin; Yong Dai (Journal of Zhejiang University-SCIENCE B, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Heme Oxygenase-2 Suppress TNF-α and IL6 Expression via TLR4/MyD88-Dependent Signaling Pathway in Mouse Cerebral Vascular Endothelial Cells - Ren-Jin Chen; Hong-Hua Yuan; Teng-Ye Zhang; Zhen-Zhen Wang; An-kang Hu; Lian-Lian Wu; Zhang-Ping Yang; Yong-Jiang Mao; De-Jun Ji; Xiao-Rong Zhu (Molecular Neurobiology, 2014)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Inhibition of acid-sensing ion channel 1a in hepatic stellate cells attenuates PDGF-induced activation of HSCs through MAPK pathway - Fan-rong Wu; Chun-xiao Pan; Chao Rong; Quan Xia; Feng-lai Yuan; Jie Tang; Xiao-yu Wang; Nan Wang; Wen-lin Ni; Fei-hu Chen (Molecular and Cellular Biochemistry, 2014)

Role of Interleukin-22 in liver diseases - Chun-xiao Pan; Jie Tang; Xiao-yu Wang; Fan-rong Wu; Jin-fang Ge; Fei-hu Chen (Inflammation Research, 2014)

A three‐component signalling system fine‐tunes expression kinetics of HPPK responsible for folate synthesis by positive feedback loop during stress response of X anthomonas campestris - Fang‐Fang Wang; Chao‐Ying Deng; Zhen Cai; Ting Wang; Li Wang; Xiao‐Zheng Wang; Xiao‐Ying Chen; Rong‐Xiang Fang; Wei Qian (Environmental Microbiology, 2014)
Summary During adaptation to environments, bacteria employ two‐component signal transduction systems, which contain histidine kinases and response regulators, to sense and respond to exogenous and cellular stimuli in an accurate spatio‐temporal manner. Although the protein phosphorylation process between histidine kinase and response regulator has been well documented, the molecular mechanism fine‐tuning phosphorylation levels of response regulators is comparatively less studied. Here we combined genetic and biochemical approaches to reveal that a hybrid histidine kinase, SreS , is involved in the SreK ‐ SreR phosphotransfer process to control salt stress response in the bacterium X anthomonas campestris . The N ‐terminal receiver domain of SreS acts as a phosphate sink by competing with the response regulator SreR to accept the phosphoryl group from the latter's cognate histidine kinase SreK . This regulatory process is critical for bacterial survival because the dephosphorylated SreR protein participates in activating one of the tandem promoters ( P 2) at the 5′ end of the sreK ‐ sreR ‐ sreS ‐ hppK operon, and then modulates a transcriptional surge of the stress‐responsive gene hppK , which is required for folic acid synthesis. Therefore, our study dissects the biochemical process of a positive feedback loop in which a ‘three‐component’ signalling system fine‐tunes expression kinetics of downstream genes.

The rare intracellular RET mutation p.S891A in a Chinese Han family with familial medullary thyroid carcinoma - Xiao-Ping Qi; Rong-Xin Zhang; Jin-Lin Cao; Zhen-Guang Chen; Hang-Yang Jin; Ren-Rong Yang (Journal of Biosciences, 2014)

Dynamic properties analysis of a stay cable-damper system in consideration of design and construction factors - Danhui Dan; Yanyang Chen; Rong Xiao (Earthquake Engineering and Engineering Vibration, 2014)

Light-regulated phosphorylation of maize phosphoenolpyruvate carboxykinase plays a vital role in its activity - Qing Chao; Xiao-Yu Liu; Ying-Chang Mei; Zhi-Fang Gao; Yi-Bo Chen; Chun-Rong Qian; Yu-Bo Hao; Bai-Chen Wang (Plant Molecular Biology, 2014)

A systematic proteomic analysis of NaCl-stressed germinating maize seeds - Ling-Bo Meng; Yi-Bo Chen; Tian-Cong Lu; Yue-Feng Wang; Chun-Rong Qian; Yang Yu; Xuan-Liang Ge; Xiao-Hui Li; Bai-Chen Wang (Molecular Biology Reports, 2014)

The role of HMGB1-RAGE axis in migration and invasion of hepatocellular carcinoma cell lines - Ruo-Chan Chen; Pan-Pan Yi; Rong-Rong Zhou; Mei-Fang Xiao; Ze-Bing Huang; Dao-Lin Tang; Yan Huang; Xue-Gong Fan (Molecular and Cellular Biochemistry, 2014)

An Observational Study of Autologous Bone Marrow-Derived Stem Cells Transplantation in Seven Patients with Nervous System Diseases: A 2-Year Follow-Up - Chao Ren; Run-lu Geng; Wei Ge; Xiao-Yun Liu; Hao Chen; Mei-Rong Wan; De-Qin Geng (Cell Biochemistry and Biophysics, 2014)

Arbuscular mycorrhizal fungi: potential biocontrol agents against the damaging root hemiparasite Pedicularis kansuensis? - Xiao-Lin Sui; Ai-Rong Li; Yan Chen; Kai-Yun Guan; Lu Zhuo; Yan-Yan Liu (Mycorrhiza, 2014)

Discovery of a new sesquiterpenoid from Phellinus ignarius with antiviral activity against influenza virus - Ai-Rong Song; Xiao-Le Sun; Chao Kong; Chen Zhao; Dan Qin; Fang Huang; Song Yang (Archives of Virology, 2014)

Soil nitrification and foliar δ15N declined with stand age in trembling aspen and jack pine forests in northern Alberta, Canada - Ya-Lin Hu; En-Rong Yan; Woo-Jung Choi; Francis Salifu; Xiao Tan; Z. Chi Chen; De-Hui Zeng; Scott X. Chang (Plant and Soil, 2014)

Estrogen receptor α gene PvuII polymorphism and coronary artery disease: a meta-analysis of 21 studies - Jie Ding; Hui Xu; Xiang Yin; Fu-rong Zhang; Xiao-ping Pan; Yi-an Gu; Jun-zhu Chen; Xiao-gang Guo (Journal of Zhejiang University-SCIENCE B, 2014)

Neuroglobin Promotes Neurite Outgrowth via Differential Binding to PTEN and Akt - Li Li; Qian Rong Liu; Xin Xin Xiong; Ju Mei Liu; Xiao Jing Lai; Chun Cheng; Feng Pan; Yong Chen; Shang Bin Yu; Albert Cheung Hoi Yu; Xiao Qian Chen (Molecular Neurobiology, 2014)

Characterization of microRNA expression profiles in 3T3-L1 adipocytes overexpressing C10orf116 - Jie Qiu; Xiao-guang Zhou; Xiao-yu Zhou; Chun Zhu; Chun-mei Shi; Chen-bo Ji; Rui Cheng; Yong Li; Xi-rong Guo (Molecular Biology Reports, 2013)

Are habitat fragmentation, local adaptation and isolation‐by‐distance driving population divergence in wild rice O ryza rufipogon ? - Yao Zhao; Klaas Vrieling; Hui Liao; Manqiu Xiao; Yongqing Zhu; Jun Rong; Wenju Zhang; Yuguo Wang; Ji Yang; Jiakuan Chen; Zhiping Song (Molecular Ecology, 2013)
Habitat fragmentation weakens the connection between populations and is accompanied with isolation by distance ( IBD ) and local adaptation (isolation by adaptation, IBA ), both leading to genetic divergence between populations. To understand the evolutionary potential of a population and to formulate proper conservation strategies, information on the roles of IBD and IBA in driving population divergence is critical. The putative ancestor of A sian cultivated rice ( O ryza sativa ) is endangered in C hina due to habitat loss and fragmentation. We investigated the genetic variation in 11 C hinese O ryza rufipogon populations using 79 microsatellite loci to infer the effects of habitat fragmentation, IBD and IBA on genetic structure. Historical and current gene flows were found to be rare ( m h = 0.0002–0.0013, m c = 0.007–0.029), indicating IBD and resulting in a high level of population divergence ( F ST = 0.343). High within‐population genetic variation ( H E = 0.377–0.515), relatively large effective population sizes ( N e = 96–158), absence of bottlenecks and limited gene flow were found, demonstrating little impact of recent habitat fragmentation on these populations. Eleven gene‐linked microsatellite loci were identified as outliers, indicating local adaptation. Hierarchical AMOVA and partial M antel tests indicated that population divergence of C hinese O . rufipogon was significantly correlated with environmental factors, especially habitat temperature. Common garden trials detected a significant adaptive population divergence associated with latitude. Collectively, these findings imply that IBD due to historical rather than recent fragmentation, followed by local adaptation, has driven population divergence in O . rufipogon .

What interests them in the pictures? — Differences in eyetracking between rhesus monkeys and humans - Ying-Zhou Hu; Hui-Hui Jiang; Ci-Rong Liu; Jian-Hong Wang; Cheng-Yang Yu; Synnöve Carlson; Shang-Chuan Yang; Veli-Matti Saarinen; Joshua D. Rizak; Xiao-Guang Tian; Hen Tan; Zhu-Yue Chen; et al. (Neuroscience Bulletin, 2013)

Meat quality traits of four Chinese indigenous chicken breeds and one commercial broiler stock - Rong-fa Guan; Fei Lyu; Xiao-qiang Chen; Jie-qing Ma; Han Jiang; Chao-geng Xiao (Journal of Zhejiang University-SCIENCE B, 2013)

IFNG polymorphisms are associated with tuberculosis in Han Chinese pediatric female population - Chen Shen; Wei-Wei Jiao; Wei-Xing Feng; Xi-Rong Wu; Jing Xiao; Qing Miao; Lin Sun; Bin-Bin Wang; Jing Wang; Fang Liu; Dan Shen; A-Dong Shen (Molecular Biology Reports, 2013)

Genetic diversity and population structure of Chinese Cherry revealed by chloroplast DNA trnQ-rps16 intergenic spacers variation - Tao Chen; Xiao-rong Wang; Hao-ru Tang; Qing Chen; Xiao-jiao Huang; Jiao Chen (Genetic Resources and Crop Evolution, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Role of Paraoxonase-1 in the Protection of Hydrogen Sulfide-Donating Sildenafil (ACS6) Against Homocysteine-Induced Neurotoxicity - Xiao-Qing Tang; Rong-Qian Chen; Ling Dong; Yan-Kai Ren; Piero Del Soldato; Anna Sparatore; Duan-Fang Liao (Journal of Molecular Neuroscience, 2013)

Construction of multiple shRNAs expression vector that inhibits FUT1 gene expression and production of the transgenic SCNT embryos in vitro - Jian-wen Chen; Yu Zhang; Yuan-liang Zhang; Chao Wei; Xing Liu; Na-ru Zhou; Qing Jia; Yun-sheng Li; Xiao-rong Zhang; Yun-hai Zhang (Molecular Biology Reports, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Comparison of metabolic effects of ziprasidone versus olanzapine treatment in patients with first-episode schizophrenia - Jian-Jun Ou; Yi Xu; Hong-Hui Chen; Xiaoduo Fan; Keming Gao; Juan Wang; Xiao-Feng Guo; Ren-Rong Wu; Jing-Ping Zhao (Psychopharmacology, 2013)

Flexible change and cooperation between mitochondrial electron transport and cytosolic glycolysis as the basis for chilling tolerance in tomato plants - Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; Yang-Wen-Ke Liao; Xiao-Jian Xia; Yan-Hong Zhou; Rong-Qing Wang; Zhi-Xiang Chen; Jing-Quan Yu (Planta, 2013)

The Neuroprotective Effect of Overexpression of Calbindin-D28k in an Animal Model of Parkinson’s Disease - Hong-Hua Yuan; Ren-Jin Chen; Yu-Hua Zhu; Chang-Ling Peng; Xiao-Rong Zhu (Molecular Neurobiology, 2013)

Nonstructural protein-1 of respiratory syncytial virus regulates HOX gene expression through interacting with histone - Yu-rong Tan; Dan Peng; Cui-mei Chen; Xiao-qun Qin (Molecular Biology Reports, 2013)

Methods to measure and analyze ciliary beat activity: Ca2+ influx-mediated cilia mechanosensitivity - Wen-Er Li; Weiwei Chen; Yun-Fei Ma; Qing-Rong Tuo; Xiao-Jing Luo; Ting Zhang; Wen-Bo Sai; Jing Liu; Jinhua Shen; Zhi-Gang Liu; Yun-Min Zheng; Yong-Xiao Wang; et al. (Pflügers Archiv - European Journal of Physiology, 2012)

Identification and characterization of a gene encoding a putative lysophosphatidyl acyltransferase from Arachis hypogaea - Si-Long Chen; Jia-Quan Huang; Yong Lei; Yue-Ting Zhang; Xiao-Ping Ren; Yu-Ning Chen; Hui-Fang Jiang; Li-Ying Yan; Yu-Rong Li; Bo-Shou Liao (Journal of Biosciences, 2012)

Tetrandrine citrate eliminates imatinib-resistant chronic myeloid leukemia cells in vitro and in vivo by inhibiting Bcr-Abl/β-catenin axis - Xiao-hua Xu; Yi-chao Gan; Gen-bo Xu; Ting Chen; Hong Zhou; Jin-fen Tang; Ying Gu; Fei Xu; Ying-ying Xie; Xiao-ying Zhao; Rong-zhen Xu (Journal of Zhejiang University-SCIENCE B, 2012)

Effectiveness of soil N availability indices in predicting site productivity in the oil sands region of Alberta - En-Rong Yan; Ya-Lin Hu; Francis Salifu; Xiao Tan; Z. Chi Chen; Scott X. Chang (Plant and Soil, 2012)

Neuroprotection by Silencing iNOS Expression in a 6-OHDA Model of Parkinson’s Disease - Min Li; Fu-rong Dai; Xiao-ping Du; Qi-dong Yang; Yuxiang Chen (Journal of Molecular Neuroscience, 2012)

Changes of wetland landscape patterns in Dadu River catchment from 1985 to 2000, China - Laibin Huang; Junhong Bai; Denghua Yan; Bin Chen; Rong Xiao; Haifeng Gao (Frontiers of Earth Science, 2012)

(−)-Epigallocatechin-3-gallate inhibits the replication cycle of hepatitis C virus - Chao Chen; Hui Qiu; Jian Gong; Qing Liu; Han Xiao; Xin-Wen Chen; Bin-Lian Sun; Rong-Ge Yang (Archives of Virology, 2012)

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)

Functional analysis of the HS185 regulatory element in the rice HSP70 promoter - Yu-Man Zhang; Yu-Mei Zheng; Na Xiao; Li-Na Wang; Yao Zhang; Rong-Xiang Fang; Xiao-Ying Chen (Molecular Biology Reports, 2012)

Interleukin-23 as a potential therapeutic target for rheumatoid arthritis - Chao Rong; Wei Hu; Fan-rong Wu; Xiao-juan Cao; Fei-hu Chen (Molecular and Cellular Biochemistry, 2012)

Caudatin induces cell cycle arrest and caspase-dependent apoptosis in HepG2 cell - Hong Rong Fei; Hong Lei Chen; Ting Xiao; Geng Chen; Feng Ze Wang (Molecular Biology Reports, 2012)

Single nucleotide polymorphism of CACNA2D1 gene and its association with milk somatic cell score in cattle - Zheng Rong Yuan; Jiao Li; Li Liu; Lu Pei Zhang; Li Min Zhang; Cui Chen; Xiao Jie Chen; Xue Gao; Jun Ya Li; Jin Bao Chen; Hui Jiang Gao; Shang Zhong Xu (Molecular Biology Reports, 2011)

Synthesis of novel 6-triazologlycolipids via click chemistry and their preliminary cytotoxicity assessments - Hai-Lin Zhang; Xiao-Peng He; Li Sheng; Yuan Yao; Wei Zhang; Xiao-Xin Shi; Jia Li; Guo-Rong Chen (Molecular Diversity, 2011)

A recessive gene controlling male sterility sensitive to short daylength/low temperature in wheat (Triticum aestivum L.) - Xiao-dong Chen; Dong-fa Sun; De-fu Rong; Jun-hua Peng; Cheng-dao Li (Journal of Zhejiang University-SCIENCE B, 2011)

Isolation of a buprofezin co-metabolizing strain of Pseudomonas sp. DFS35-4 and identification of the buprofezin transformation pathway - Kai Chen; Xiao-Mei Liu; Rong Li; Yuan Liu; Hai Hu; Shun-Peng Li; Jian-Dong Jiang (Biodegradation, 2011)

Discovering the distinct inhibitory effects between C4-epimeric glycosyl amino acids: new insight into the development of protein tyrosine phosphatase inhibitors - Xiao-Peng He; Cui Li; Zhi-Zhou Wang; Li-Xin Gao; Xiao-Xin Shi; Yun Tang; Juan Xie; Jia Li; Guo-Rong Chen; Kaixian Chen (Glycoconjugate Journal, 2011)

Inhibition of Endogenous Hydrogen Sulfide Generation is Associated with Homocysteine-Induced Neurotoxicity: Role of ERK1/2 Activation - Xiao-Qing Tang; Xin-Tian Shen; Yi-E Huang; Rong-Qian Chen; Yan-Kai Ren; Heng-Rong Fang; Yuan-Yuan Zhuang; Chun-Yan Wang (Journal of Molecular Neuroscience, 2011)

Monitoring of flow field based on stable isotope geochemical characteristics in deep groundwater - Lu-wang Chen; He-rong Gui; Xiao-xi Yin (Environmental Monitoring and Assessment, 2011)

Contamination characteristics of heavy metals in wetland soils along a tidal ditch of the Yellow River Estuary, China - Junhong Bai; Laibin Huang; Denghua Yan; Qinggai Wang; Haifeng Gao; Rong Xiao; Chen Huang (Stochastic Environmental Research and Risk Assessment, 2011)

Overexpression of PGC-1β improves insulin sensitivity and mitochondrial function in 3T3-L1 adipocytes - Chun-Lin Gao; Guang-Ling Liu; Shi Liu; Xiao-Hui Chen; Chen-Bo Ji; Chun-Mei Zhang; Zheng-Kun Xia; Xi-rong Guo (Molecular and Cellular Biochemistry, 2011)

Lingo2 variants associated with essential tremor and Parkinson’s disease - Yi-Wen Wu; K. M. Prakash; Tian-Yi Rong; Hui-Hua Li; Qin Xiao; Louis C. Tan; Wing-Lok Au; Jian-qing Ding; Sheng-di Chen; Eng-King Tan (Human Genetics, 2011)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

Genistein alters caffeine exposure in healthy female volunteers - Yao Chen; Chang-Qiong Xiao; Yi-Jing He; Bi-Lian Chen; Guo Wang; Gan Zhou; Wei Zhang; Zhi-Rong Tan; Shan Cao; Li-Ping Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2011)

A Proteomic Investigation of B Lymphocytes in an Autistic Family: A Pilot Study of Exposure to Natural Rubber Latex (NRL) May Lead to Autism - Chen Shen; Xin-liang Zhao; Weina Ju; Xiao-bing Zou; Li-rong Huo; Wu Yan; Jun-hua Zou; Guo-di Yan; Edmund C. Jenkins; W. Ted Brown; Nanbert Zhong (Journal of Molecular Neuroscience, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Plantagiolide F, a minor withanolide from Tacca plantaginea - Jun-Yun Yang; Chang-Xiang Chen; Rong-Hua Zhao; Xiao-Jiang Hao; Hai-Yang Liu (Natural Product Research, 2011)

Analysis of the antibodies anti-Toxoplasma gondii by ELISA based on two diagnostic antigens: rSAG1 and rBAG1 - Min Liu; Tao Wang; Hua Li; Ju-Ying Li; Han Zhong; Chang-Zan Tan; De-Cheng Huang; Liang Zhao; Xiao-Guang Chen; Zhao-Rong Lun (Acta Parasitologica, 2011)
Schizophrenia is a serious neuropsychiatric disease of uncertain etiology. Previous studies have demonstrated that antibodies to Toxoplasma gondii infection are associated with an increased risk of schizophrenia. The objective of this study was to analyze anti-T. gondii antibodies in 477 Chinese schizophrenia patients using an enzyme-linked immunosorbent assay (ELISA) based on recombinant surface antigen 1 (rSAG1), recombinant bradyzoite antigen 1 (rBAG1) and the soluble tachyzoite antigens (STAg) of T. gondii RH strain. Results showed that among the sero-positives (IgG and/or IgM) for T. gondii infection examined in schizophrenia patients, sero-positive samples for rSAG1, rBAG1 and STAg were 20.5% (98/477), 20.5% (98/477) and 23.5% (112/477) respectively, while compared to 210 blood donors, sero-positive (IgG and/or IgM) samples for these antigens (rSAG1, rBAG1 and STAg) were only 5.7% (12/210), 6.2% (13/210) and 5.7% (12/210), respectively. Furthermore, when IgG antibody reaction in the schizophrenia sera was compared with the rBAG1 and rSAG1, results demonstrated that beside the cases which can be detected by both rSAG1 and rBAG1, some sero-positive for T. gondii in schizophrenia sera can only be detected either by rSAG1 or rBAG1. This phenomenon was also observed in the detection of IgM with rSAG1 and rBAG1. 5.9% (28/477) of cases of schizophrenia which are positive for IgG or IgM by rSAG1 are negative for STAg, while 9.2% (44/477) of the schizophrenia cases which are positive for IgG or IgM by rBAG1 are negative for STAg. Although STAg can also be used to diagnose T. gondii infection from schizophrenia patients, it may not actually indicate the infection as some positive samples may be mistakenly considered to be negative. In conclusion, our results demonstrate that the sero-positive rate for T. gondii in the Chinese schizophrenia patients was higher than blood donors. More importantly, our results provide evidence that the combination of rSAG1 and rBAG1 antigens in the diagnosis of T. gondii infection could closely reflect the actual infection of this parasite in schizophrenia patients.

Effects of erythromycin on voriconazole pharmacokinetics and association with CYP2C19 polymorphism - Hui-Yan Shi; Jin Yan; Wen-Hui Zhu; Guo-Ping Yang; Zhi-Rong Tan; Wei-Hua Wu; Gan Zhou; Xiao-Ping Chen; Dong-Sheng Ouyang (European Journal of Clinical Pharmacology, 2010)

NYGGF4 homologous gene expression in 3T3-L1 adipocytes: regulation by FFA and adipokines - Ya-ping Zhao; Chun-mei Zhang; Chun Zhu; Xiao-hui Chen; Jia-lin Wang; Chen-bo Ji; Xia Chi; Qin Hong; Yu-zhu Peng; Xi-rong Guo (Molecular Biology Reports, 2010)

Diversity and Antimicrobial and Plant-Growth-Promoting Activities of Endophytic Fungi in Dendrobium loddigesii Rolfe - Xiao Mei Chen; Hai Ling Dong; Ke Xing Hu; Zhi Rong Sun; Juan Chen; Shun Xing Guo (Journal of Plant Growth Regulation, 2010)

A preliminary study of the Six-Item Screener in detecting cognitive impairment - Mei-Rong Chen; Qi-Hao Guo; Xin-Yi Cao; Zhen Hong; Xiao-Hong Liu (Neuroscience Bulletin, 2010)

Karyotype and genetic relationship based on RAPD markers of six wild buckwheat species (Fagopyrum spp.) from southwest of China - Xiao-yan Yang; Zhen-Fang Wu; Hui Chen; Ji-rong Shao; Qi Wu (Genetic Resources and Crop Evolution, 2010)

Efficient production of omega-3 fatty acid desaturase (sFat-1)-transgenic pigs by somatic cell nuclear transfer - DengKe Pan; Li Zhang; YanRong Zhou; Chong Feng; Chuan Long; Xiao Liu; Rong Wan; Jian Zhang; AiXing Lin; EnQiu Dong; ShuChen Wang; HouGang Xu; et al. (Science China Life Sciences, 2010)

Gene expression profiles in the prefrontal cortex of SHR rats by cDNA microarrays - Jie Qiu; Qin Hong; Rong-hua Chen; Mei-ling Tong; Min Zhang; Li Fei; Xiao-qin Pan; Mei Guo; Xi-rong Guo; Xia Chi (Molecular Biology Reports, 2010)

Identification of QTLs for yield and yield components of barley under different growth conditions - Da-wei Xue; Mei-xue Zhou; Xiao-qin Zhang; Song Chen; Kang Wei; Fan-rong Zeng; Ying Mao; Fei-bo Wu; Guo-ping Zhang (Journal of Zhejiang University-SCIENCE B, 2010)

Cytological and RAPD data revealed genetic relationships among nine selected populations of the wild bramble species, Rubus parvifolius and R. coreanus (Rosaceae) - Xiao-rong Wang; Yuan Liu; Bi-feng Zhong; Xiao-li Dong; Qing Chen; Wu-feng Xia; Hanwu Zhang; Hao-ru Tang (Genetic Resources and Crop Evolution, 2010)

Association of functional polymorphisms in MMPs genes with gastric cardia adenocarcinoma and esophageal squamous cell carcinoma in high incidence region of North China - Yan Li; Dong-lan Sun; Ya-nan Duan; Xiao-juan Zhang; Na Wang; Rong-miao Zhou; Zhi-feng Chen; Shi-jie Wang (Molecular Biology Reports, 2010)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Resistin induces rat insulinoma cell RINm5F apoptosis - Chun-lin Gao; De-yu Zhao; Jie Qiu; Chun-mei Zhang; Chen-bo Ji; Xiao-hui Chen; Feng Liu; Xi-rong Guo (Molecular Biology Reports, 2009)

Molecular interaction between prion protein and GFAP both in native and recombinant forms in vitro - Chen-Fang Dong; Xiao-Fan Wang; Xin Wang; Song Shi; Gui-Rong Wang; Bing Shan; Run An; Xiao-Li Li; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2008)

Systematic biotic responses to palaeoenvironmental change in the Late Pleistocene southern South China Sea: a preliminary study - Muhong Chen; Qianyu Li; Lanlan Zhang; Fan Zheng; Jun Lu; Rong Xiang; Lili Zhang; Wen Yan; Zhong Chen; Shangbin Xiao (Journal of Quaternary Science, 2008)
Oxygen and carbon isotopes from the planktonic foraminifer Globigerinoides sacculifer , trace element contents, calcium carbonate, biogenic silica, grain size, and abundances of diatoms, radiolarians and foraminifera in a deep‐sea core from the southwestern South China Sea were analysed to investigate the response of various marine ecological communities to environmental changes over the last 200 ka. The synthesised results show that the quality of the palaeoecological environment for biological growth is primarily affected by nutrient supply and terrigenous disturbance. Ba and P are important nutrient elements for the growth of diatoms, radiolarians and planktonic foraminifera. Together with dissolved silica and calcium carbonate in sea water, these elements may control microbiotic development. However, variations in Fe content appear to affect diatom and radiolarian abundance. Optimal biotic growth occurs when nutrients are abundant and when there is minimal terrigenous disturbance. Biotic growth decreases when sea water is highly oligotrophic and terrigenous input is high. Maximum biological growth occurred in the mid Holocene, but deteriorated soon afterwards owing to increased terrigenous input, causing a decrease of biological abundance and productivity in the late Holocene. The results also indicate how the Toba volcanic eruption ca. 74 ka ago contributed to changing the ecological environment in the southern South China Sea. Copyright © 2008 John Wiley & Sons, Ltd.

Development of the male reproductive structures in Taxus yunnanensis - Bing-Yi Wang; Jian-Rong Su; Danilo D. Fernando; Zong-Hui Yang; Zhi-Jun Zhang; Xiao-Ming Chen; Yan-Ping Zhang (Plant Systematics and Evolution, 2008)

Isolation and identification of Sclerotinia stem rot causal pathogen in Arabidopsis thaliana - Ai-rong Wang; Wen-wei Lin; Xiao-ting Chen; Guo-dong Lu; Jie Zhou; Zong-hua Wang (Journal of Zhejiang University-SCIENCE B, 2008)

Dysregulation of CREB binding protein triggers thrombin-induced proliferation of vascular smooth muscle cells - Jing Chen; Hong Jiang; Lin Xu; Li-Hua Zhu; Lang Wang; Hua-Zhi Wen; Xiao-Rong Hu (Molecular and Cellular Biochemistry, 2008)

Different expression patterns of CK2 subunits in the brains of experimental animals and patients with transmissible spongiform encephalopathies - Jian-Ming Chen; Chen Gao; Qi Shi; Bing Shan; Yan-Jun Lei; Chen-Fang Dong; Run An; Gui-Rong Wang; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Archives of Virology, 2008)

A new dibenzofuran and other constituents from Ligularia caloxantha , a chinese medicinal plant - Shu-Yun Shi; Ming-Hui Hu; Di-Yao Wu; Chang-Xin Zhou; Jian-Xia Mo; Juan-Hua Xu; Liu-Rong Chen; Hui Dou; Hua Peng; Xiao-Jiang Hao; Joachim Stöckigt; Yu Zhao (Natural Product Research, 2008)

Secretion of malate and citrate from roots is related to high Al-resistance in Lespedeza bicolor - Xiao Ying Dong; Ren Fang Shen; Rong Fu Chen; Zhao Liang Zhu; Jian Feng Ma (Plant and Soil, 2008)

Adenovirus-mediated PDCD5 gene transfer sensitizes K562 cells to apoptosis induced by idarubicin in vitro and in vivo - Guo-Rui Ruan; Hong-Shan Zhao; Yan Chang; Jin-Lan Li; Ya-Zhen Qin; Yan-Rong Liu; Shan-Shan Chen; Xiao-Jun Huang (Apoptosis, 2008)

Persistence and dissipation of synthetic pyrethroid pesticides in red soils from the Yangtze River Delta area - Xiao-zhi Gu; Gang-ya Zhang; Li Chen; Rong-ling Dai; Yuan-chun Yu (Environmental Geochemistry and Health, 2008)

Polymorphisms in intron 1 of the porcinePOU1F1 gene - Cheng-Yi Song; Bo Gao; Shang-Hui Teng; Xiao-Yang Wang; Fei Xie; Guo-hong Chen; Zhi-Yue Wang; Rong-bin Jing; Jiu-De Mao (Journal of Applied Genetics, 2007)

Heregulin protects mesenchymal stem cells from serum deprivation and hypoxia-induced apoptosis - Chun Gui; Jian An Wang; Ai Na He; Tie Long Chen; Rong Hua Luo; Jun Jiang; Xin Yang Hu; Xiao Jie Xie (Molecular and Cellular Biochemistry, 2007)

Improving human micronutrient nutrition through biofortification in the soil–plant system: China as a case study - Xiao-E. Yang; Wen-Rong Chen; Ying Feng (Environmental Geochemistry and Health, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Hepatoprotective effect of a protein-enriched fraction from the maggots (Musca domestica) against CCl4-induced hepatic damage in rats - Fu-Rong Wang; Hui Ai; Xiao-Min Chen; Chao-Liang Lei (Biotechnology Letters, 2007)

Phenotypic plasticity rather than locally adapted ecotypes allows the invasive alligator weed to colonize a wide range of habitats - Yu-Peng Geng; Xiao-Yun Pan; Cheng-Yuan Xu; Wen-Ju Zhang; Bo Li; Jia-Kuan Chen; Bao-Rong Lu; Zhi-Ping Song (Biological Invasions, 2007)

Bone marrow mesenchymal stem cell transplantation combined with perindopril treatment attenuates infarction remodelling in a rat model of acute myocardial infarction - Jian-an Wang; Rong-hua Luo; Xing Zhang; Xiao-jie Xie; Xin-yang Hu; Ai-na He; Jie Chen; Jia-hui Li (Journal of Zhejiang University-SCIENCE B, 2006)

The role of CYP2C19 in amitriptyline N-demethylation in Chinese subjects - Zhi-Ping Jiang; Yan Shu; Xiao-Ping Chen; Song-Lin Huang; Rong-Hua Zhu; Wei Wang; Nan He; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2002)